Adhesive composition, and optical laminate including adhesive layer

JP2026167559APending Publication Date: 2026-10-14SUMITOMO CHEM CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2026048950
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2025-03-31
Filing Date
2026-03-24
Publication Date
2026-10-14

AI Technical Summary

Benefits of technology

【0007】 本発明によれば、良好な耐久性を示す光学積層体をもたらす接着剤組成物を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2026167559000001
    Figure 2026167559000001
  • Figure 2026167559000002
    Figure 2026167559000002
  • Figure 2026167559000003
    Figure 2026167559000003
Patent Text Reader

Abstract

To provide an adhesive composition that results in an optical laminate exhibiting good durability. [Solution] An adhesive composition comprising a curable compound, wherein the curable compound comprises (A) a urethane acrylate compound having 2 or more (meth)acrylic groups and a weight-average molecular weight of 1000 g / mol or more, (B) a (meth)acrylate compound having 2 or more (meth)acrylic groups and a hydroxyl group in the molecule, (C) a (meth)acrylate compound having 1 (meth)acrylic group and a hydroxyl group in the molecule, and (D) a compound that does not have a hydroxyl group in the molecule but has a carboxyl group and a polymerizable group.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] The present invention relates to an adhesive composition and an optical laminate including an adhesive layer. [Background technology]

[0002] In recent years, with the demand for thinner image display panels and the like, thin-film phase difference films and / or polarizing films formed from compositions containing liquid crystal compounds have been used as constituent elements. For example, Patent Document 1 discloses a polarizing film in which a first resin layer, a polarizer, an alignment film, and a second resin layer are laminated in this order, wherein the polarizer is a cured product of a polarizer-forming composition containing a polymerizable liquid crystal compound having a (meth)acrylic group and a dichroic dye, and it is also disclosed that this polarizing film may be laminated with a phase difference film formed from a composition containing a liquid crystal compound. [Prior art documents] [Patent Documents]

[0003] [Patent Document 1] Japanese Patent Publication No. 2020-56834 [Overview of the project] [Problems that the invention aims to solve]

[0004] A polarizing film (polarizer) formed from a composition containing a polymerizable liquid crystal compound and a dichroic dye may experience a decrease in polarization performance over time due to the disruption of anisotropy, depending on the environmental conditions to which it is exposed, as the dichroic dye contained in the polarizing film is more likely to diffuse out of the polarizing film. In recent years, image display devices have been used in a variety of environments, and consequently, there is a growing demand for further improvements in the durability of optical laminates that have polarization performance. The present invention aims to provide an adhesive composition that results in an optical laminate exhibiting good durability. [Means for solving the problem]

[0005] The inventors of this invention have diligently studied and, as a result, completed the present invention. Specifically, the present invention encompasses the following embodiments.

[0006] [1] An adhesive composition comprising a curable compound, The curable compound is (A) A urethane acrylate compound having 2 or more (meth)acrylic groups and a weight-average molecular weight of 1000 g / mol or more. (B) A (meth)acrylate compound having two or more (meth)acrylic groups and a hydroxyl group in the molecule, (C) A (meth)acrylate compound having 1 (meth)acrylic group and a hydroxyl group in the molecule, and (D) Compounds that do not have a hydroxyl group in the molecule but have a carboxyl group and a polymerizable group. An adhesive composition containing the following: [2] The adhesive composition according to [1], further comprising (meth)acrylate compound (E) having 1 (meth)acrylic group and having an aromatic ring without a hydroxyl group in the molecule. [3] The adhesive composition according to [1] or [2], wherein the content of the urethane acrylate compound (A) is 3 to 30 parts by mass per 100 parts by mass of the total amount of curable compounds contained in the adhesive composition. [4] The adhesive composition according to any one of [1] to [3], wherein the content of the (meth)acrylate compound (B) is 3 to 30 parts by mass per 100 parts by mass of the total amount of curable compounds contained in the adhesive composition. [5] The adhesive composition according to any one of [1] to [4], wherein the content of the (meth)acrylate compound (C) is 15 to 80 parts by mass per 100 parts by mass of the total amount of curable compounds contained in the adhesive composition. [6] The adhesive composition according to any one of [1] to [5], wherein the content of compound (D) is 5 to 45 parts by mass per 100 parts by mass of the total amount of curable compounds contained in the adhesive composition. [7] The adhesive composition according to any one of [2] to [6], wherein the content of the (meth)acrylate compound (E) is 5 to 25 parts by mass per 100 parts by mass of the total amount of curable compounds contained in the adhesive composition. [8] The adhesive composition according to any one of [1] to [7], further comprising a polymerization initiator, wherein the content of the polymerization initiator is 1 to 10 parts by mass per 100 parts by mass of the total amount of curable compounds contained in the adhesive composition. [9] The polymerization initiator has a molar extinction coefficient of 10 L·mol in acetonitrile solvent at a light source wavelength of 400 nm. -1 ·cm -1 The adhesive composition described above [8].

[10] An optical laminate comprising a polarizing film and an adhesive layer adjacent to each other, The polarizing film comprises a cured layer of a polymerizable liquid crystal composition containing a polymerizable liquid crystal compound and a dichroic dye. The adhesive layer is a cured layer of the adhesive composition described in any of [1] to [9], wherein the optical laminate is an optical laminate.

[11] The optical laminate according to

[10] , wherein the adhesive layer contains a phase difference film adjacent to the side opposite to the polarizing film, and the phase difference film contains a cured layer of a polymerizable liquid crystal composition containing a polymerizable liquid crystal compound.

[12] The optical laminate according to

[11] , wherein the phase difference film includes an alignment film, and the alignment film is located on the adhesive layer side.

[13] When the in-plane average refractive index of the polarizing film is n1, the in-plane average refractive index of the adhesive layer is n2, and the in-plane average refractive index of the phase difference film is n3, then the following equation (1): |(n1×n3) 1 / 2 -n²| ≤ 0.070 (1) An optical laminate according to

[11] or

[12] that satisfies the following conditions. [Effects of the Invention]

[0007] According to the present invention, it is possible to provide an adhesive composition that results in an optical laminate exhibiting good durability. [Modes for carrying out the invention]

[0008] [Adhesive composition] The adhesive composition of the present invention comprises a curable compound, the curable compound is (A) A urethane acrylate compound having 2 or more (meth)acrylic groups and a weight-average molecular weight of 1000 g / mol or more. (B) A (meth)acrylate compound having two or more (meth)acrylic groups and a hydroxyl group in the molecule, (C) A (meth)acrylate compound having 1 (meth)acrylic group and a hydroxyl group in the molecule, and (D) Compounds that do not have a hydroxyl group in the molecule but have a carboxyl group and a polymerizable group. Includes.

[0009] The present inventors have found that by including a curable compound containing the above components (A) to (D) in the adhesive composition, an optical laminate containing an adhesive layer, which is the cured layer of the adhesive composition, and a polarizing film adjacent to each other can exhibit good durability. This is not intended to be limited to any particular theory, but it is thought that by including a curable compound containing specific components in the adhesive composition, an adhesive layer with good flexibility and good adhesion to adjacent layers can be obtained, thereby suppressing the time-dependent migration of the dichroic dye contained in the polarizing film to the adhesive layer when an optical laminate containing an adhesive layer and a polarizing film adjacent to each other is fabricated.

[0010] <Curable compound> From the viewpoint of providing durability for the optical laminate, the content of the curable compound in the adhesive composition is preferably 70 to 100% by mass, more preferably 80 to 99% by mass, even more preferably 90 to 99% by mass, and particularly preferably 96 to 98% by mass, relative to the mass of the adhesive composition.

[0011] The curable compound includes a urethane acrylate compound (A) having two or more (meth)acrylic groups and a weight-average molecular weight of 1000 g / mol or more. The urethane acrylate compound (A) is not particularly limited as long as it is a urethane (meth)acrylate compound having two or more (meth)acrylic groups in its molecule and a weight-average molecular weight of 1000 g / mol or more; known urethane (meth)acrylate compounds can be used. From the viewpoint of durability of the optical laminate, the number of (meth)acrylic groups contained in the molecule of urethane acrylate compound (A) is preferably three or more, more preferably four or more, preferably nine or less, and more preferably seven or less. The weight-average molecular weight of urethane acrylate compound (A) is preferably 1050 g / mol or more, preferably 20000 g / mol or less, and more preferably 3000 g / mol or less. The weight-average molecular weight can be measured, for example, by gel permeation chromatography (GPC). The urethane acrylate compound (A) can be used alone or in combination of two or more types. When using two or more types of urethane acrylate compound (A), the weight-average molecular weight of the urethane acrylate compound (A) is calculated according to the mass ratio of the urethane acrylate compound (A) used. In this specification, the term "(meth)acrylic" means "acrylic" or "methacrylic," and similarly, the term "(meth)acrylate" means "acrylate" or "methacrylate."

[0012] From the viewpoint of providing durability for the optical laminate, the content of the urethane acrylate compound (A) is preferably 3 to 30 parts by mass, more preferably 5 to 28 parts by mass, even more preferably 5 to 20 parts by mass, and particularly preferably 10 to 20 parts by mass, based on 100 parts by mass of the total amount of curable compounds contained in the adhesive composition.

[0013] The curable compound includes (B) a (meth)acrylate compound having two or more (meth)acrylic groups and a hydroxyl group in the molecule. Here, (meth)acrylate compound (B) is different from urethane acrylate compound (A). The number of (meth)acrylic groups contained in the molecule of (meth)acrylate compound (B) is preferably 6 or less, more preferably 3 or less. The number of hydroxyl groups contained in the molecule of (meth)acrylate compound (B) is 1 or more, preferably 6 or less, more preferably 2 or less. Examples of (meth)acrylate compounds (B) include (meth)acrylate compounds having two acrylic groups and a hydroxyl group in the molecule, specifically 2-hydroxy-3-methacrylate, 2-hydroxypropane-1,3-diyldiaacrylate, 2-hydroxypropane-1,3-diylbis(2-methylacrylate), 3-(3-(acryloyloxy)-2-hydroxypropoxy)-2-hydroxypropyl methacrylate, 5-hydroxy-1,3-phenylenebis(2-methylacrylate); and (meth)acrylate compounds having three acrylic groups and a hydroxyl group in the molecule. Examples of acrylate compounds include 2-((acryloyloxy)methyl)-2-(hydroxymethyl)propane-1,3-diyl diacrylate and ((2-(((acryloyloxy)methoxy)methyl)-2-(hydroxymethyl)propane-1,3-diyl)bis(oxy))bis(methylene) diacrylate; and (meth)acrylate compounds having 5 acrylic groups and a hydroxyl group in the molecule, specifically 2-((3-(acryloyloxy)-2,2-bis((acryloyloxy)methyl)propoxy)methyl)-2-(hydroxymethyl)propane-1,3-diyl diacrylate. (Meth)acrylate compound (B) can be used alone or in combination of two or more types.

[0014] From the viewpoint of providing durability for the optical laminate, the content of (meth)acrylate compound (B) is preferably 3 to 30 parts by mass, more preferably 3 to 25 parts by mass, even more preferably 3 to 20 parts by mass, and particularly preferably 5 to 10 parts by mass, based on 100 parts by mass of the total amount of curable compounds contained in the adhesive composition.

[0015] The curable compound includes a (meth)acrylate compound having one (meth)acrylic group and a hydroxyl group in the molecule. The number of hydroxyl groups contained in the molecule of (meth)acrylate compound (C) is one or more, preferably four or less, and more preferably three or less. Examples of (meth)acrylate compound (C) include hydroxyalkyl (meth)acrylates having 4 to 16 carbon atoms, hydroxycycloalkyl (meth)acrylates having 4 to 16 carbon atoms, hydroxyalkylated phenyl (meth)acrylates having 2 to 14 carbon atoms, polyethylene glycol (meth)acrylate, hydroxy(di)alkyl (meth)acrylamides having 4 to 16 carbon atoms, hydroxyalkylated phenyl (meth)acrylamides having 2 to 14 carbon atoms, polyethylene glycol (meth)acrylamide, and the like. Preferred examples are hydroxyalkyl (meth)acrylates having 4 to 8 carbon atoms and hydroxycycloalkyl (meth)acrylates having 4 to 16 carbon atoms, and more preferred examples are hydroxyalkyl acrylates having 4 to 8 carbon atoms and hydroxycycloalkyl acrylates having 4 to 16 carbon atoms. In one embodiment of the present invention, (meth)acrylate compound (C) preferably contains hydroxyalkyl acrylates having 4 to 8 carbon atoms, and more preferably contains 4-hydroxybutyl acrylate. (Meth)acrylate compound (C) can be used alone or in combination of two or more types.

[0016] From the viewpoint of providing durability for the optical laminate, the content of (meth)acrylate compound (C) is preferably 15 to 80 parts by mass, more preferably 25 to 70 parts by mass, even more preferably 30 to 60 parts by mass, and particularly preferably 40 to 55 parts by mass, based on 100 parts by mass of the total amount of curable compounds contained in the adhesive composition. In one embodiment of the present invention, when the adhesive composition contains two or more (meth)acrylate compounds (C), the content of hydroxyalkyl (meth)acrylate having 4 to 8 carbon atoms (preferably 4-hydroxybutyl acrylate) is preferably 30% by mass or more, more preferably 50% by mass or more, even more preferably 70% by mass or more, particularly preferably 80% by mass or more, and may be 100% by mass, based on the total amount of (meth)acrylate compounds (C) contained in the adhesive composition.

[0017] The curable compounds include compounds (D) that do not have a hydroxyl group in the molecule but have a carboxyl group and a polymerizable group. Here, compound (D) is different from urethane acrylate compound (A) and (meth)acrylate compound (E) described later. Examples of polymerizable groups include vinyl group, (meth)acrylic group, vinyloxy group and (meth)acrylicoxy group. Compound (D) has one or more polymerizable groups, and if it has two or more polymerizable groups, they may be the same or different. Examples of compound (D) include acrylic acid, methacrylic acid, mono(2-acryloyloxyethyl) succinate, 2-(acryloyloxy)acetic acid, 3-(acryloyloxy)propanoic acid, 2-(methacryloyloxy)acetic acid, 3-(methacryloyloxy)propanoic acid, 4-(acryloyloxy)benzoic acid, and 4-(methacryloyloxy)benzoic acid. Acrylic acid, methacrylic acid, and mono(2-acryloyloxyethyl) succinate are preferred, and acrylic acid and methacrylic acid are more preferred. Compound (D) can be used alone or in combination of two or more.

[0018] From the viewpoint of providing durability for the optical laminate, the content of compound (D) is preferably 5 to 45 parts by mass, more preferably 10 to 40 parts by mass, even more preferably 15 to 30 parts by mass, and particularly preferably 15 to 25 parts by mass, based on 100 parts by mass of the total amount of curable compounds contained in the adhesive composition. In one embodiment of the present invention, compound (D) preferably contains acrylic acid and / or methacrylic acid in an amount of 50% by mass or more, more preferably 70% by mass or more, and even more preferably 80% by mass or more, relative to the total amount of compound (D) contained in the adhesive composition. Including acrylic acid and / or methacrylic acid as the main component of compound (D) can be expected to further improve the durability of the resulting optical laminate.

[0019] In one preferred embodiment of the present invention, from the viewpoint of providing an optical laminate having an improved refractive index, the curable compound further comprises a (meth)acrylate compound having 1 (meth)acrylic group, no hydroxyl group in the molecule, and one or more aromatic rings. The number of aromatic rings contained in the (meth)acrylate compound (E) is preferably 2 or more, preferably 4 or less, and more preferably 3 or less. Examples of aromatic rings include benzene rings, biphenyl rings, and polycyclic aromatic rings. When the (meth)acrylate compound (E) contains multiple aromatic rings, they may be the same or different from each other. Examples of (meth)acrylate compounds (E) include ethoxylated-o-phenylphenol acrylate, bisphenol A type epoxy (meth)acrylate, bisphenol F type epoxy (meth)acrylate, 2-([1,1'-biphenyl]-2-yloxy)ethyl acrylate, 3-phenoxybenzyl acrylate, naphthalene-1-yl methyl acrylate, 2-(2-([1,1'-biphenyl]-2-yloxy)ethoxy)ethyl acrylate, methyl (naphthalene-1-ylmethoxy)acrylate, 6-((4'-cyano-[1,1'-biphenyl]-4-yl)oxy)hexyl acrylate, 4-benzoylphenyl acrylate, anthracene-9-yl methyl acrylate, and [1,1'-biphenyl)-4,4'-diyl diacrylate, with ethoxylated-o-phenylphenol acrylate being preferred. (Meth)acrylate compound (E) may be used alone or in combination of two or more types.

[0020] When the curable compound contains a (meth)acrylate compound (E), the content of the (meth)acrylate compound (E) is preferably 5 to 25 parts by mass, more preferably 10 to 20 parts by mass, and even more preferably 10 to 15 parts by mass, based on 100 parts by mass of the total amount of curable compounds contained in the adhesive composition.

[0021] As long as the effects of the present invention are not hindered, the curable compound may contain one or more curable compounds other than urethane acrylate compound (A), (meth)acrylate compound (B), (meth)acrylate compound (C), compound (D), and (meth)acrylate compound (E). Examples of such curable compounds include monofunctional (meth)acrylate compounds that do not have a hydroxyl group, a carboxyl group, or an aromatic ring, and (meth)acrylate compounds that have an acrylamide group. When using such a curable compound, the content of the curable compound is preferably 1 to 30 parts by mass, more preferably 5 to 25 parts by mass, even more preferably 5 to 15 parts by mass, and particularly preferably 5 to 10 parts by mass, based on 100 parts by mass of the total amount of the curable compound.

[0022] The curable compound preferably contains one or more monofunctional (meth)acrylates and one or more polyfunctional (meth)acrylates. A monofunctional (meth)acrylate is a (meth)acrylate having one (meth)acrylic group in its molecule, and a polyfunctional (meth)acrylate is a (meth)acrylate having two or more (meth)acrylic groups in its molecule. The number of (meth)acrylic groups contained in the molecule of a polyfunctional (meth)acrylate is usually 20 or less. The urethane acrylate compound (A) and (meth)acrylate compound (B) described above are included in polyfunctional (meth)acrylates because they have two or more (meth)acrylic groups, while the (meth)acrylate compound (C) and (meth)acrylate compound (E) described above are included in monofunctional (meth)acrylates because they have one (meth)acrylic group.

[0023] In a preferred embodiment of the present invention, from the viewpoint of providing durability of the optical laminate, the content of the polyfunctional (meth)acrylate is preferably 5 to 75 parts by mass, more preferably 10 to 45 parts by mass, still more preferably 15 to 35 parts by mass, and particularly preferably 20 to 30 parts by mass, relative to 100 parts by mass of the total amount of curable compounds contained in the adhesive composition.

[0024] In another preferred embodiment of the present invention, from the viewpoint of providing durability of the optical laminate, the content of the monofunctional (meth)acrylate is preferably 25 to 90 parts by mass, more preferably 30 to 80 parts by mass, still more preferably 40 to 70 parts by mass, and particularly preferably 50 to 65 parts by mass, relative to 100 parts by mass of the total amount of curable compounds contained in the adhesive composition.

[0025] In one embodiment of the present invention, the ratio of the mass of the polyfunctional (meth)acrylate to the total mass of the monofunctional (meth)acrylate and compound (D) contained in the curable compound [mass of polyfunctional (meth)acrylate / (total mass of monofunctional (meth)acrylate and compound (D))] is preferably 0.10 to 0.99, more preferably 0.20 to 0.60, and particularly preferably 0.30 to 0.45. When the ratio is within the above range, an optical laminate having excellent durability can be obtained.

[0026] <Polymerization Initiator> The adhesive composition preferably contains a polymerization initiator in addition to the curable compound. In a preferred embodiment of the present invention, the polymerization initiator has a molar extinction coefficient at a light source wavelength of 400 nm in an acetonitrile solvent of preferably 10 L·mol -1 ·cm -1 or more, more preferably 100 L·mol -1 ·cm -1 or more, still more preferably 500 L·mol -1 ·cm -1 or more, and particularly preferably 1000 L·mol -1 ·cm -1The above is the case. When the molar extinction coefficient of the polymerization initiator is equal to or greater than the lower limit, the polymerization reaction proceeds sufficiently, and a diffusion suppression effect of the dichroic dye and excellent adhesion to the adjacent layer can be expected. The upper limit of the molar extinction coefficient of the polymerization initiator is not particularly limited, and is usually 3000 L·mol. -1 ·cm -1 The following are listed below.

[0027] Examples of polymerization initiators include benzoin compounds, benzophenone compounds, alkylphenone compounds, acylphosphine oxide compounds, triazine compounds, iodonium salts, and sulfonium salts. Polymerization initiators can be used individually or in combination of two or more.

[0028] Examples of benzoin compounds include benzoin, benzoin methyl ether, benzoin ethyl ether, benzoin isopropyl ether, and benzoin isobutyl ether. Examples of benzophenone compounds include benzophenone, o-methyl benzoylbenzoate, 4-phenylbenzophenone, 4-benzoyl-4'-methyldiphenyl sulfide, 3,3',4,4'-tetra(tert-butylperoxycarbonyl)benzophenone, and 2,4,6-trimethylbenzophenone. Examples of alkylphenone compounds include diethoxyacetophenone, 2-methyl-2-morpholino-1-(4-methylthiophenyl)propan-1-one, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)butan-1-one, 2-hydroxy-2-methyl-1-phenylpropan-1-one, 1,2-diphenyl-2,2-dimethoxyethane-1-one, 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]propan-1-one, 1-hydroxycyclohexylphenyl ketone, and oligomers of 2-hydroxy-2-methyl-1-[4-(1-methylvinyl)phenyl]propan-1-one. Examples of acylphosphine oxide compounds include 2,4,6-trimethylbenzoyldiphenylphosphine oxide and bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide. Examples of triazine compounds include 2,4-bis(trichloromethyl)-6-(4-methoxyphenyl)-1,3,5-triazine, 2,4-bis(trichloromethyl)-6-(4-methoxynaphthyl)-1,3,5-triazine, 2,4-bis(trichloromethyl)-6-(4-methoxystyryl)-1,3,5-triazine, and 2,4-bis(trichloromethyl)-6-[2-(5-methylfuran-2-yl)ethenyl Examples include triazines such as 2,4-bis(trichloromethyl)-6-[2-(furan-2-yl)ethenyl]-1,3,5-triazine, 2,4-bis(trichloromethyl)-6-[2-(4-diethylamino-2-methylphenyl)ethenyl]-1,3,5-triazine, and 2,4-bis(trichloromethyl)-6-[2-(3,4-dimethoxyphenyl)ethenyl]-1,3,5-triazine.

[0029] Commercially available polymerization initiators can also be used. Examples of commercially available polymerization initiators include Irgacure® 907, 184, 651, 819, 250, and 369 (manufactured by Ciba Specialty Chemicals Co., Ltd.); Omnirad 819, Omnirad 907, Esacure 1001M, Esacure KIP160 (manufactured by IDM Resins BV); Seiko Chemicals® BZ, Z, and BEE (manufactured by Seiko Chemicals Ltd.); Kayacure® BP100 and UVI-6992 (manufactured by Dow Chemical Ltd.); Adeka Optomer SP-152 and SP-170 (manufactured by ADEKA Corporation); TAZ-A and TAZ-PP (manufactured by Nippon Siber Hegner Co., Ltd.); TAZ-104 (manufactured by Sanwa Chemical Co., Ltd.).

[0030] If the adhesive composition contains a polymerization initiator, the amount of polymerization initiator is preferably 1 to 10 parts by mass, more preferably 2 to 8 parts by mass, even more preferably 2 to 5 parts by mass, and particularly preferably 2.5 to 3.5 parts by mass, based on 100 parts by mass of the total amount of curable compounds contained in the adhesive composition.

[0031] <Additives> The adhesive composition may contain additives commonly used in adhesive compositions, in addition to the curable compound and polymerization initiator, as long as the effects of the present invention are not hindered. Examples of such additives include sensitizers, polymerization inhibitors, leveling agents, ion trapping agents, antioxidants, chain transfer agents, polymerization accelerators (such as polyols), sensitizing aids, light stabilizers, tackifiers, thermoplastic resins, fillers, flow regulators, plasticizers, defoamers, silane coupling agents, dyes, antistatic agents, and ultraviolet absorbers. Additives can be used individually or in combination of two or more. When the adhesive composition contains additives, the amount of additives should be a commonly used amount and should be appropriately selected depending on the type of additive.

[0032] The method for preparing the adhesive composition is not particularly limited and can be prepared by mixing and stirring a curable compound, and optionally a polymerization initiator and the aforementioned additives, using general methods. The inventors have also found that by selecting specific compounds (A) to (D) as curable compounds to be included in the adhesive composition of the present invention, improved applicability of the adhesive composition can be achieved. This is not intended to be limited to any particular theory, but it is thought that selecting specific compounds (A) to (D) results in good compatibility of those components and high affinity with the vicinity of the adjacent layer surface. The improvement in the applicability of the adhesive composition can be better achieved by employing the embodiments described herein, in particular the embodiments described as preferred.

[0033] [Optical laminate] The optical laminate in the present invention is an optical laminate comprising a polarizing film and an adhesive layer adjacent to each other, wherein the adhesive layer is a cured layer of an adhesive composition containing the curable compound described above. The cured layer of an adhesive composition containing a curable compound is a layer obtained by applying the adhesive composition to obtain a coating film, and then curing (polymerizing) the curable compound contained in the coating film; that is, the cured layer of the adhesive composition containing the curable compound is a layer comprising a cured product (polymer) of the curable compound. The adhesive layer has the function of bonding a polarizing film adjacent to one side of the adhesive layer with a layer or film adjacent to the other side.

[0034] As described above, the adhesive composition of the present invention has improved applicability. Therefore, a more uniform coating film can be obtained with a desired thickness, which can lead to better adhesion between the adhesive layer and adjacent layers, and can lead to improved durability of the optical laminate. Furthermore, as described above, the adhesive composition of the present invention can form an adhesive layer with good flexibility and good adhesion to adjacent layers, and it is thought that this suppresses the time-dependent migration of the dichroic dye contained in the polarizing film to the adhesive layer when an optical laminate containing the adhesive layer and the polarizing film adjacent to each other is manufactured, and as a result the optical laminate can have improved durability. Thus, the adhesive composition of the present invention can be suitably used in the manufacture of an optical laminate containing the adhesive layer, which is the cured product layer of the adhesive composition, and the polarizing film adjacent to each other, and the resulting optical laminate can have improved durability.

[0035] <Adhesive layer> The adhesive layer can be formed by applying an adhesive composition to obtain a coating film, and then curing the curable compound contained in the coating film. The adhesive composition is applied to the adhesive layer and adjacent layers or films. These adjacent layers or films include polarizing films and phase difference films.

[0036] Examples of methods for applying adhesive compositions include known methods such as spin coating, extrusion, gravure coating, die coating, bar coating, and applicator coating; and printing methods such as flexographic coating.

[0037] The curing of the adhesive composition is preferably carried out by irradiating it with active energy rays to polymerize polymerizable components such as (meth)acrylate contained in the adhesive composition. The active energy rays are appropriately selected depending on the type of polymerizable component such as (meth)acrylate, the type of polymerization initiator and their amounts, etc. Specific examples of active energy rays include one or more active energy rays selected from the group consisting of visible light, ultraviolet light, infrared light, X-rays, alpha rays, beta rays, and gamma rays. Among these, ultraviolet light is preferred from the viewpoint of ease of control of the polymerization reaction and / or the use of photopolymerization equipment that is widely used in this field.

[0038] Examples of light sources for active energy rays include low-pressure mercury lamps, medium-pressure mercury lamps, high-pressure mercury lamps, ultra-high-pressure mercury lamps, xenon lamps, halogen lamps, carbon arc lamps, tungsten lamps, gallium lamps, excimer lasers, LED light sources emitting in the wavelength range of 380-440 nm, chemical lamps, black light lamps, microwave-excited mercury lamps, and metal halide lamps.

[0039] The UV irradiation intensity is typically 10 to 10,000 mW / cm². 2 The ultraviolet irradiation intensity is preferably in the wavelength range effective for activating the polymerization initiator. The irradiation time is usually 0.1 seconds to 10 minutes, preferably 0.5 seconds to 5 minutes, more preferably 1 second to 2 minutes, and even more preferably 1 second to 1 minute. When irradiation is performed once or multiple times at such ultraviolet irradiation intensity, the integrated light amount is 10 to 3,000 mJ / cm² as the integrated light amount at a wavelength of 280 to 320 nm (UV-B region). 2 Preferably 50 to 2,000 mJ / cm² 2 More preferably 100-1,000 mJ / cm² 2 That is the case.

[0040] When an adhesive composition is applied to a polarizing film, an adhesive layer can be formed by bringing an adjacent layer (e.g., a phase difference film) into contact with the resulting coated film and irradiating it with active energy rays from either the polarizing film side or the adjacent layer side. When an adhesive composition is applied to an adjacent layer (e.g., a phase difference film) on the opposite side of the polarizing film, an adhesive layer can be formed by bringing a polarizing film into contact with the resulting coated film and irradiating it with active energy rays from either the adjacent layer side or the polarizing film side. The contact surface of the layer or film that comes into contact with the coating film of the adhesive composition may be subjected to surface treatment such as corona treatment or plasma treatment.

[0041] The thickness of the adhesive layer is not particularly limited, but is generally 10 μm or less, preferably 0.15 to 5 μm, more preferably 0.5 to 4 μm, and even more preferably 1 to 3 μm. The thickness of the adhesive layer, as well as the polarizing film, liquid crystal polarizing film, alignment film, phase difference film, and liquid crystal phase difference film described later, can be measured by a laser microscope or a film thickness gauge, respectively.

[0042] <Polarizing film> The optical laminate includes a polarizing film adjacent to the adhesive layer. The polarizing film includes a cured layer of a polymerizable liquid crystal composition containing a polymerizable liquid crystal compound and a dichroic dye. The polarizing film consists of a cured layer of a polymerizable liquid crystal composition containing a polymerizable liquid crystal compound and a dichroic dye (liquid crystal polarizing film), or consists of a liquid crystal polarizing film and an alignment film adjacent to the liquid crystal polarizing film. When the polarizing film consists of a liquid crystal polarizing film and an alignment film adjacent to the liquid crystal polarizing film, in the optical laminate, the liquid crystal polarizing film may be located on the adhesive layer side, or the alignment film may be located on the adhesive layer side. From the viewpoint of the manufacturing process, it is preferable that the liquid crystal polarizing film is located on the adhesive layer side. Furthermore, when the liquid crystal polarizing film is adjacent to the adhesive layer, the liquid crystal polarizing film and the adhesive layer are in direct contact, so the effect of suppressing the migration of the dichroic dye from the liquid crystal polarizing film to the adhesive layer (and therefore the effect on the durability of the optical laminate) can be confirmed more significantly than when the liquid crystal polarizing film is located via an alignment film.

[0043] (Liquid crystal polarizing film) A liquid crystal polarizing film is a cured layer of a polymerizable liquid crystal composition (hereinafter also referred to as "liquid crystal polarizing film forming composition") containing a polymerizable liquid crystal compound and a dichroic dye. In such a liquid crystal polarizing film, the dichroic dye is encapsulated in the polymerizable liquid crystal compound, and the polymerizable liquid crystal compound and the dichroic dye are polymerized and cured in an oriented state. However, when an adhesive layer is placed adjacent to the polarizing film, in conventional adhesive layers, the dichroic dye contained in the liquid crystal polarizing film may migrate to the adhesive layer (especially in high-temperature environments), causing a decrease in polarization performance over time. In the present invention, since the composition forming the adhesive layer (adhesive composition) contains specific compounds (A) to (D), such migration of the dichroic dye is suppressed even in high-temperature environments, and as a result, the optical laminate exhibits excellent durability even in high-temperature environments. In this specification, durability in high-temperature environments refers to the characteristic of being able to suppress a decrease in polarization performance, such as changes in polarization degree or transmittance, even when exposed to high-temperature environments for a long time, and increased or improved durability in high-temperature environments refers to a decrease or change in polarization performance being less.

[0044] In the optical laminate of the present invention, the polymerizable liquid crystal compound (hereinafter sometimes referred to as "polymerizable liquid crystal compound (A)") contained in the liquid crystal polarizing film forming composition is preferably a liquid crystal compound having at least one (meth)acrylic group, and more preferably a liquid crystal compound having two or more (meth)acrylic groups from the viewpoint of improving the adhesion and heat resistance of the optical laminate. Furthermore, polymerizable liquid crystal compound (A) may also contain polymerizable groups other than (meth)acrylic groups. A polymerizable group is a group that can participate in the polymerization reaction by active radicals or acids generated from the polymerization initiator. Examples of polymerizable groups other than (meth)acrylic groups include vinyl groups, vinyloxy groups, 1-chlorovinyl groups, isopropenyl groups, 4-vinylphenyl groups, oxiranyl groups, and oxetanyl groups. In the present invention, from the viewpoint of the adhesion and heat resistance of the optical laminate, the polymerizable groups of polymerizable liquid crystal compound (A) are preferably composed of (meth)acrylic groups, and more preferably composed of (meth)acrylooxy groups.

[0045] In the present invention, the polymerizable liquid crystal compound (A) is preferably a compound that exhibits smectic liquid crystal properties. By using a polymerizable liquid crystal compound that exhibits smectic liquid crystal properties, a liquid crystal polarizing film with a high degree of orientation order can be formed. The liquid crystal state exhibited by the polymerizable liquid crystal compound (A) is preferably a smectic phase (smectic liquid crystal state), and more preferably a higher-order smectic phase (higher-order smectic liquid crystal state) from the viewpoint of achieving a higher degree of orientation order. Here, the higher-order smectic phase refers to smectic B phase, smectic D phase, smectic E phase, smectic F phase, smectic G phase, smectic H phase, smectic I phase, smectic J phase, smectic K phase, and smectic L phase, and among these, smectic B phase, smectic F phase, and smectic I phase are more preferred. The liquid crystalline properties can be either thermotropic or lyotropic, but thermotropic liquid crystalline properties are preferred because they allow for precise control of film thickness. Furthermore, the polymerizable liquid crystal compound (A) may be a monomer, an oligomer formed by polymerization of polymerizable groups, or a polymer.

[0046] The polymerizable liquid crystal compound (A) is preferably a liquid crystal compound having at least one (meth)acrylic group. Such a liquid crystal compound is not particularly limited, and known polymerizable liquid crystal compounds can be used, but compounds exhibiting smectic liquid crystal properties are preferred. Examples of such polymerizable liquid crystal compounds include the compound represented by the following formula (A1) (hereinafter sometimes referred to as "polymerizable liquid crystal compound (A1)"). U 1 -V 1 -W 1 -(X 1 -Y 1 -) n -X 2 -W 2 -V 2 -U 2 (A1) [In formula (A1), X 1 and X 2Each of these independently represents a divalent aromatic group or a divalent alicyclic hydrocarbon group, where the hydrogen atoms in the divalent aromatic group or divalent alicyclic hydrocarbon group may be substituted with halogen atoms, C1-C4 alkyl groups, C1-C4 fluoroalkyl groups, C1-C4 alkoxy groups, cyano groups, or nitro groups, and the carbon atoms constituting the divalent aromatic group or divalent alicyclic hydrocarbon group may be substituted with oxygen atoms, sulfur atoms, or nitrogen atoms. However, X 1 and X 2 At least one of these is a optionally substituted 1,4-phenylene group or an optionally substituted cyclohexane-1,4-diyl group. Y 1 It is a single bond or a divalent linking group. n is 1 to 3, and if n is 2 or greater, multiple X 1 They may be the same or they may be different. 2 is multiple X 1 It may be the same as or different from any or all of the following. Also, if n is 2 or more, there may be multiple Y 1 These values ​​may be the same or different. From the viewpoint of liquid crystalline properties, n is preferably 2 or greater. U 1 represents a hydrogen atom or a (meth)acryloxy group. U 2 This represents a (meth)acryloxy group. W 1 and W 2 These are, independently of each other, single or divalent linking groups. V 1 and V 2 Each of these independently represents an alkanediyl group having 1 to 20 carbon atoms, which may have substituents, and the -CH2- constituting the alkanediyl group may be replaced with -O-, -CO-, -S-, or NH-.

[0047] In polymerizable liquid crystal compound (A1), X 1 and X 2These are, independently of each other, preferably a substituted 1,4-phenylene group or a substituted cyclohexane-1,4-diyl group, X 1 and X 2 At least one of these is an optionally substituted 1,4-phenylene group or an optionally substituted cyclohexane-1,4-diyl group, preferably a trans-cyclohexane-1,4-diyl group. Optional substituents on the optionally substituted 1,4-phenylene group or the optionally substituted cyclohexane-1,4-diyl group include C1-C4 alkyl groups such as methyl, ethyl, and butyl groups, cyano groups, and halogen atoms such as chlorine and fluorine atoms. It is preferably unsubstituted.

[0048] Furthermore, polymerizable liquid crystal compound (A1) is a compound of formula (A1-1): -(X 1 -Y 1 -) n -X 2 - (A1-1) [In the formula, X 1 , Y 1 , X 2 And n have the same meaning as above. From the viewpoint of enabling the expression of smectic liquid crystal properties, it is preferable that the portion indicated by [hereinafter referred to as substructure (A1-1)] has an asymmetric structure. A polymerizable liquid crystal compound (A1) in which the substructure (A1-1) is an asymmetric structure is, for example, one in which n is 1 and one X 1 and X 2 A polymerizable liquid crystal compound (A1) in which the two have different structures is also an example. 1 Compounds in which two X have the same structure 1 They have the same structure as each other, and one X 2 These two X 1 Polymerizable liquid crystal compound (A1) has a different structure from two X 1 W 1 X that binds 1 However, the other X 1 and X2 It has a different structure, and the other X 1 and X 2 Another example is the polymerizable liquid crystal compound (A1) which has the same structure as the others. Furthermore, n is 3, and there are three Y 1 Compounds in which the three X's are identical in structure 1 and one X 2 A polymerizable liquid crystal compound (A1) is one in which one of the structures is different from all three others.

[0049] Y 1 -CH2CH2-, -CH2O-, -CH2CH2O-, -COO-, -OCOO-, single bond, -N=N-, -CR a =CR b -, -C≡C-, -CR a =N- or CO-NR a - is preferable. a and R b Each of these independently represents a hydrogen atom or an alkyl group having 1 to 4 carbon atoms. 1 It is more preferably -CH2CH2-, -COO-, or a single bond, and multiple Y 1 If X 2 Y that combines with 1 It is more preferable that it be -CH2CH2- or -CH2O-. 1 and X 2 If all have the same structure, then two or more Y have different bonding methods. 1 It is preferable that multiple Ys with different coupling methods exist. 1 When present, an asymmetric structure is formed, which tends to allow smectic liquid crystal properties to be exhibited.

[0050] U 2 This is a (meth)acryloxy group. 1 is a hydrogen atom or a (meth)acrylooxy group, preferably a (meth)acrylooxy group. From the viewpoint of improving the adhesion between layers and heat resistance of the optical laminate, U 1 and U 2are preferably both (meth)acryloxy groups. The (meth)acryloxy group may be in a polymerized state or in an unpolymerized state, and is preferably in an unpolymerized state.

[0051] V 1 and V 2 Examples of the alkanediyl group represented by include methylene group, ethylene group, propane-1,3-diyl group, butane-1,3-diyl group, butane-1,4-diyl group, pentane-1,5-diyl group, hexane-1,6-diyl group, heptane-1,7-diyl group, octane-1,8-diyl group, decane-1,10-diyl group, tetradecane-1,14-diyl group, icosane-1,20-diyl group and the like. V 1 and V 2 is preferably an alkanediyl group having 2 to 12 carbon atoms, and more preferably an alkanediyl group having 6 to 12 carbon atoms.

[0052] Examples of the substituent that the alkanediyl group optionally has include a cyano group, a halogen atom and the like, and the alkanediyl group is preferably unsubstituted, more preferably an unsubstituted linear alkanediyl group.

[0053] W 1 and W 2 each independently preferably represent a single bond, -O-, -S-, -COO- or -OCOO-, more preferably a single bond or -O-.

[0054] In addition, when the molecular structure has an asymmetric molecular structure, the polymerizable liquid crystal compound tends to exhibit smectic liquid crystallinity. Specific examples of such a structure include the partial structures of the following (A-a) to (A-i). Accordingly, the polymerizable liquid crystal compound (A) is more preferably a polymerizable liquid crystal compound having the partial structures of the following (A-a) to (A-i) and exhibiting smectic liquid crystallinity. From the viewpoint of being capable of exhibiting high-order smectic liquid crystallinity, it is more preferable to have the partial structure of (A-a), (A-b) or (A-c). In the following (A-a) to (A-i), * represents a bond (single bond).

[0055] [ka]

[0056] Examples of polymerizable liquid crystal compounds (A) include those represented by formulas (A-1) to (A-25). When polymerizable liquid crystal compound (A) has a cyclohexane-1,4-diyl group, it is preferable that the cyclohexane-1,4-diyl group is in trans form.

[0057] [ka]

[0058] [ka]

[0059] [ka]

[0060] Among these, at least one selected from the group consisting of compounds represented by formulas (A-2), (A-3), (A-4), (A-5), (A-6), (A-7), (A-8), (A-13), (A-14), (A-15), (A-16), and (A-17) is preferred. As the polymerizable liquid crystal compound (A), one type may be used alone, or two or more types may be used in combination.

[0061] Polymerizable liquid crystal compound (A) can be produced by known methods, such as those described in Lub et al., Recl. Trav. Chim. Pays-Bas, 115, 321-328 (1996), or Japanese Patent No. 4719156.

[0062] In the present invention, the liquid crystal polarizing film forming composition may contain polymerizable liquid crystal compounds other than polymerizable liquid crystal compound (A). However, from the viewpoint of obtaining a liquid crystal polarizing film with a high degree of orientation order, the ratio of polymerizable liquid crystal compound (A) to the total mass of all polymerizable liquid crystal compounds contained in the liquid crystal polarizing film forming composition is preferably 51% by mass or more, more preferably 70% by mass or more, and even more preferably 90% by mass or more.

[0063] Furthermore, if the liquid crystal polarizing film forming composition contains two or more polymerizable liquid crystal compounds (A), at least one of them may be polymerizable liquid crystal compound (A1), or all of them may be polymerizable liquid crystal compound (A1). By combining multiple polymerizable liquid crystal compounds, it may be possible to temporarily maintain liquid crystalline properties even at temperatures below the liquid crystal-crystal phase transition temperature.

[0064] The content of polymerizable liquid crystal compounds in the liquid crystal polarizing film forming composition is preferably 40 to 99.9% by mass, more preferably 60 to 99% by mass, and even more preferably 70 to 99% by mass, relative to the solid content of the liquid crystal polarizing film forming composition. When the content of polymerizable liquid crystal compounds is within the above range, the orientation of the polymerizable liquid crystal compounds tends to be high. In this specification, solid content refers to the total amount of components excluding the solvent from the liquid crystal polarizing film forming composition.

[0065] In the present invention, the liquid crystal polarizing film forming composition comprises a dichroic dye. Here, a dichroic dye means a dye having different absorbances in the long axis direction and in the short axis direction of the molecule. The dichroic dye that can be used in the present invention is not particularly limited as long as it has the above properties, and may be a dye or a pigment. Furthermore, two or more dyes or pigments may be used in combination, or a dye and a pigment may be used in combination. In addition, the dichroic dye may be polymerizable or liquid crystalline.

[0066] As a dichroic pigment, it has a maximum absorption wavelength (λ) in the range of 300-700 nm. MAX) is preferred. Examples of such dichroic dyes include acridine dyes, oxazine dyes, cyanine dyes, naphthalene dyes, azo dyes, anthraquinone dyes, and the like.

[0067] Examples of the azo dyes include monoazo dyes, bisazo dyes, trisazo dyes, tetrakisazo dyes, stilbene azo dyes, and the like, with bisazo dyes and trisazo dyes being preferred, and examples thereof include the compound represented by formula (I) (hereinafter also referred to as "Compound (I)"). K 1 -(N=N-K 2 ) p -N=N-K 3 (I) [In formula (I), K 1 and K 3 each independently represent a phenyl group which may have a substituent, a naphthyl group which may have a substituent, or a monovalent heterocyclic group which may have a substituent. K 2 represents a p-phenylene group which may have a substituent, a naphthalene-1,4-diyl group which may have a substituent, or a divalent heterocyclic group which may have a substituent. p represents an integer of 1 to 4. When p is an integer of 2 or more, a plurality of K 2 may be the same as or different from each other. The -N=N- bond may be replaced with a -C=C-, -COO-, -NHCO-, or -N=CH- bond within a range that exhibits absorption in the visible region.]

[0068] Examples of the monovalent heterocyclic group include groups obtained by removing one hydrogen atom from a heterocyclic compound such as quinoline, thiazole, benzothiazole, thienothiazole, imidazole, benzimidazole, oxazole, and benzoxazole. Examples of the divalent heterocyclic group include groups obtained by removing two hydrogen atoms from the aforementioned heterocyclic compound.

[0069] K 1 and K 3 the phenyl group, naphthyl group and monovalent heterocyclic group in, as well as K 2The p-phenylene group, naphthalene-1,4-diyl group, and divalent heterocyclic group in this compound may optionally have substituents such as C1-C20 alkyl groups, C1-C20 alkyl groups with polymerizable groups, C1-C4 alkenyl groups; C1-C20 alkoxy groups such as methoxy, ethoxy, and butoxy groups; C1-C20 alkoxy groups with polymerizable groups; C1-C4 fluorinated alkyl groups such as trifluoromethyl groups; cyano groups; nitro groups; halogen atoms; substituted or unsubstituted amino groups such as amino groups, diethylamino groups, and pyrrolidino groups (a substituted amino group means an amino group having one or two C1-C6 alkyl groups, an amino group having one or two C1-C6 alkyl groups with polymerizable groups, or an amino group in which two substituted alkyl groups are bonded to each other to form a C2-C8 alkanediyl group. An unsubstituted amino group is -NH2). Examples of polymerizable groups include acrylic groups, methacrylic groups, acrylicoxy groups, and methacrylooxy groups.

[0070] Among the compounds (I), compounds represented by any of the following formulas (I-1) to (I-8) are preferred. [ka] [In equations (I-1) to (I-8), B 1 ~B 30 These independently represent a hydrogen atom, a C1-C6 alkyl group, a C1-C6 alkenyl group, a C1-C4 alkoxy group, a cyano group, a nitro group, a substituted or unsubstituted amino group (the definitions of substituted and unsubstituted amino groups are as described above), a chlorine atom, or a trifluoromethyl group. n1 to n4 represent integers from 0 to 3, independently of each other. If n1 is 2 or more, multiple B 2 They may be the same or different from each other. If n2 is 2 or more, multiple B 6 They may be the same or different from each other. If n3 is 2 or more, multiple B 9They may be the same or different from each other. If n4 is 2 or more, multiple B 14 They may be the same or different from each other.

[0071] As the anthraquinone dye, compounds represented by formula (I-9) are preferred. [ka] [In formula (I-9), R 1 ~R 8 These are, independently of each other, hydrogen atoms, -R x -NH2, -NHR x , -NR x 2, -SR x Alternatively, it represents a halogen atom. R x This represents an alkyl group with 1 to 4 carbon atoms or an aryl group with 6 to 12 carbon atoms.

[0072] As the oxazone dye, a compound represented by formula (I-10) is preferred. [ka] [In formula (I-10), R 9 ~R 15 These are, independently of each other, hydrogen atoms, -R x -NH2, -NHR x , -NR x 2, -SR x Alternatively, it represents a halogen atom. R x This represents an alkyl group with 1 to 4 carbon atoms or an aryl group with 6 to 12 carbon atoms.

[0073] As the acridine dye, a compound represented by formula (I-11) is preferred. [ka] [In formula (I-11), R 16 ~R 23These are, independently of each other, hydrogen atoms, -R x -NH2, -NHR x , -NR x 2, -SR x Alternatively, it represents a halogen atom. R x This represents an alkyl group with 1 to 4 carbon atoms or an aryl group with 6 to 12 carbon atoms. In equations (I-9), (I-10), and (I-11), R x Examples of alkyl groups having 1 to 6 carbon atoms include methyl, ethyl, propyl, butyl, pentyl, and hexyl groups, while examples of aryl groups having 6 to 12 carbon atoms include phenyl, toluyl, xylyl, and naphthyl groups.

[0074] As the cyanine dye, compounds represented by formula (I-12) and compounds represented by formula (I-13) are preferred. [ka] [In formula (I-12), D 1 and D 2 These represent, independently of each other, a base represented by any of the formulas (I-12a) to (I-12d). [ka] n5 represents an integer between 1 and 3. [ka] [In formula (I-13), D 3 and D 4 These represent, independently of each other, a base represented by any of the formulas (I-13a) to (I-13h). [ka] n6 represents an integer between 1 and 3.

[0075] Among these dichroic dyes, azo dyes are suitable for producing liquid crystal polarizing films with excellent polarization performance due to their high linearity. However, in optical laminates containing high-performance liquid crystal polarizing films, even the diffusion of a very small amount of dye outside the liquid crystal polarizing film has a significant impact on its optical properties. In such liquid crystal polarizing films, the present invention provides a composition that forms the adhesive layer containing specific compounds (A) to (D), which effectively suppresses the diffusion of dichroic dyes even in high-temperature environments, thereby effectively suppressing the deterioration of polarization performance. In one embodiment of the present invention, the dichroic dye contained in the liquid crystal polarizing film forming composition is preferably an azo dye.

[0076] In the present invention, the weight-average molecular weight of the dichroic dye is typically 300 to 2000 g / mol, preferably 400 to 1000 g / mol.

[0077] In one embodiment of the present invention, the dichroic dye contained in the liquid crystal polarizing film forming composition is preferably hydrophobic. When the dichroic dye is hydrophobic, the compatibility between the dichroic dye and the polymerizable liquid crystal compound (A) is improved, and the dichroic dye and the polymerizable liquid crystal compound (A) form a uniform phase state, making it possible to obtain a liquid crystal polarizing film with a high degree of orientation order. In this invention, a hydrophobic dichroic dye means a dye whose solubility in 100g of water at 25°C is 1g or less.

[0078] The content of the dichroic dye in the liquid crystal polarizing film forming composition can be appropriately determined depending on the type of dichroic dye used, but is preferably 0.1 to 50 parts by mass, more preferably 0.1 to 20 parts by mass, and even more preferably 0.1 to 12 parts by mass, per 100 parts by mass of polymerizable liquid crystal compound. When the content of the dichroic dye is within the above range, it is less likely to disrupt the orientation of the polymerizable liquid crystal compound (A), and a liquid crystal polarizing film with a high degree of orientation order can be obtained.

[0079] In the present invention, the liquid crystal polarizing film forming composition for forming a liquid crystal polarizing film may contain a polymerization initiator. The polymerization initiator is a compound that can initiate the polymerization reaction of a polymerizable liquid crystal compound (A), and a photopolymerization initiator is preferred in that it can initiate the polymerization reaction under lower temperature conditions. Specifically, photopolymerization initiators that can generate active radicals or acids by the action of light are mentioned, and among these, photopolymerization initiators that generate radicals by the action of light are preferred. Polymerization initiators can be used alone or in combination of two or more types.

[0080] As photopolymerization initiators, known photopolymerization initiators can be used. For example, photopolymerization initiators that generate active radicals include self-cleaving type photopolymerization initiators and hydrogen abstraction type photopolymerization initiators. Self-cleaving photopolymerization initiators such as self-cleaving benzoin compounds, acetophenone compounds, hydroxyacetophenone compounds, α-aminoacetophenone compounds, oxime ester compounds, acylphosphine oxide compounds, and azo compounds can be used. As hydrogen abstraction type photopolymerization initiators, hydrogen abstraction type benzophenone compounds, benzoin ether compounds, benzyl ketal compounds, dibenzosverone compounds, anthraquinone compounds, xanthone compounds, thioxanthone compounds, halogenoacetophenone compounds, dialkoxyacetophenone compounds, halogenobisimidazole compounds, halogenotriazine compounds, triazine compounds, etc. can be used.

[0081] Iodonium salts and sulfonium salts can be used as photopolymerization initiators that generate acid.

[0082] Among these, reactions at low temperatures are preferred from the viewpoint of preventing the dissolution of the dye, and self-cleaving photopolymerization initiators are preferred from the viewpoint of reaction efficiency at low temperatures, with acetophenone compounds, hydroxyacetophenone compounds, α-aminoacetophenone compounds, and oxime ester compounds being particularly preferred.

[0083] Examples of photopolymerization initiators include the following: Benzoin compounds such as benzoin, benzoin methyl ether, benzoin ethyl ether, benzoin isopropyl ether, and benzoin isobutyl ether; Hydroxyacetophenone compounds such as oligomers of 2-hydroxy-2-methyl-1-phenylpropan-1-one, 1,2-diphenyl-2,2-dimethoxyethane-1-one, 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]propan-1-one, 1-hydroxycyclohexylphenyl ketone, and 2-hydroxy-2-methyl-1-[4-(1-methylvinyl)phenyl]propan-1-one; α-aminoacetophenone compounds such as 2-methyl-2-morpholino-1-(4-methylthiophenyl)propan-1-one and 2-dimethylamino-2-benzyl-1-(4-morpholinophenyl)butan-1-one; Oxime ester compounds such as 1,2-octanedione, 1-[4-(phenylthio)-,2-(O-benzoyl oxime)], ethanone, 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazole-3-yl]-,1-(O-acetyl oxime); Acylphosphine oxide compounds such as 2,4,6-trimethylbenzoyldiphenylphosphine oxide and bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide; Benzophenone compounds such as benzophenone, o-methyl benzoylbenzoate, 4-phenylbenzophenone, 4-benzoyl-4'-methyldiphenyl sulfide, 3,3',4,4'-tetra(tert-butylperoxycarbonyl)benzophenone, and 2,4,6-trimethylbenzophenone; Dialkoxyacetophenone compounds such as diethoxyacetophenone; 2,4-Bis(trichloromethyl)-6-(4-methoxyphenyl)-1,3,5-triazine, 2,4-Bis(trichloromethyl)-6-(4-methoxynaphthyl)-1,3,5-triazine, 2,4-Bis(trichloromethyl)-6-(4-methoxystyryl)-1,3,5-triazine, 2,4-Bis(trichloromethyl)-6-[2-(5-methylfuran-2-yl)ethenyl]-1,3,5- Triazine compounds such as lyazine, 2,4-bis(trichloromethyl)-6-[2-(furan-2-yl)ethenyl]-1,3,5-triazine, 2,4-bis(trichloromethyl)-6-[2-(4-diethylamino-2-methylphenyl)ethenyl]-1,3,5-triazine, and 2,4-bis(trichloromethyl)-6-[2-(3,4-dimethoxyphenyl)ethenyl]-1,3,5-triazine. The photopolymerization initiator may be appropriately selected from the above photopolymerization initiators in relation to the polymerizable liquid crystal compound contained in the liquid crystal polarizing film forming composition.

[0084] Alternatively, commercially available photopolymerization initiators may be used. Examples of commercially available polymerization initiators include Irgacure (registered trademark) 907, 184, 651, 819, 250, and 369, 379, 127, 754, OXE01, OXE02, OXE03 (manufactured by BASF); Omnirad BCIM, Esacure 1001M, Esacure KIP160 (IDM Resins). Examples include: BV Corporation; Seikaol (registered trademark) BZ, Z, and BEE (manufactured by Seiko Chemical Co., Ltd.); Kayacure (registered trademark) BP100 and UVI-6992 (manufactured by Dow Chemical Ltd.); Adeka Optomer SP-152, N-1717, N-1919, SP-170, Adeka Arclus NCI-831, Adeka Arclus NCI-930 (manufactured by ADEKA Corporation); TAZ-A and TAZ-PP (manufactured by Nippon Siber Hegner Co., Ltd.); and TAZ-104 (manufactured by Sanwa Chemical Co., Ltd.).

[0085] The content of the polymerization initiator in the liquid crystal polarizing film forming composition for forming a liquid crystal polarizing film is preferably 1 to 10 parts by mass, more preferably 1 to 8 parts by mass, even more preferably 2 to 8 parts by mass, and particularly preferably 4 to 8 parts by mass, per 100 parts by mass of polymerizable liquid crystal compound (A). When the content of the polymerization initiator is within the above range, the polymerization reaction of the polymerizable liquid crystal compound can be carried out without significantly disrupting the orientation of the polymerizable liquid crystal compound.

[0086] Furthermore, the polymerization rate of the polymerizable liquid crystal compound in the present invention is preferably 60% or more, more preferably 65% ​​or more, and even more preferably 70% or more, from the viewpoint of line contamination and handling during manufacturing.

[0087] The liquid crystal polarizing film forming composition may further contain a photosensitizer. The use of a photosensitizer can further accelerate the polymerization reaction of polymerizable liquid crystal compounds. Examples of photosensitizers include xanthone compounds such as xanthones and thioxanthones (e.g., 2,4-diethylthioxanthone, 2-isopropylthioxanthone); anthracene compounds such as anthracene and alkoxy-containing anthracene (e.g., dibutoxyanthracene); phenothiazines and rubrene. Photosensitizers can be used alone or in combination of two or more.

[0088] If the liquid crystal polarizing film forming composition contains a photosensitizer, its content can be appropriately determined according to the type and amount of polymerization initiator and polymerizable liquid crystal compound, but preferably 0.1 to 30 parts by mass, more preferably 0.5 to 10 parts by mass, and even more preferably 0.5 to 8 parts by mass per 100 parts by mass of polymerizable liquid crystal compound (A).

[0089] Furthermore, the liquid crystal polarizing film forming composition may also contain a leveling agent. The leveling agent has the function of adjusting the fluidity of the liquid crystal polarizing film forming composition and making the coating obtained by applying the liquid crystal polarizing film forming composition flatter. Specifically, surfactants are examples of such agents. As the leveling agent, at least one selected from the group consisting of leveling agents mainly composed of polyacrylate compounds and leveling agents mainly composed of fluorine atom-containing compounds is preferred. Leveling agents can be used alone or in combination of two or more types.

[0090] Examples of leveling agents primarily composed of polyacrylate compounds include "BYK-350", "BYK-352", "BYK-353", "BYK-354", "BYK-355", "BYK-358N", "BYK-361N", "BYK-380", "BYK-381", and "BYK-392" (BYK Chemie).

[0091] Examples of leveling agents whose main component is a fluorine atom-containing compound include "Megafac® R-08", "R-30", "R-90", "F-410", "F-411", "F-443", "F-445", "F-470", "F-471", "F-477", "F-479", "F-482", and "F-483" (DIC Corporation); "Surflon® S-381", "S Examples include "-382", "S-383", "S-393", "SC-101", "SC-105", "KH-40", and "SA-100" (AGC Seimi Chemical Co., Ltd.); "E1830", "E5844" (Daikin Fine Chemical Laboratories, Inc.); "F-Top EF301", "F-Top EF303", "F-Top EF351", and "F-Top EF352" (Mitsubishi Materials Electronic Chemicals Co., Ltd.).

[0092] When the composition for forming a liquid crystal polarizing film contains a leveling agent, its content is preferably 0.05 to 5 parts by mass, and more preferably 0.05 to 3 parts by mass, per 100 parts by mass of the polymerizable liquid crystal compound (A). When the content of the leveling agent is within the above range, it is easier to orient the polymerizable liquid crystal compound horizontally, and unevenness is less likely to occur, resulting in a tendency to obtain a smoother liquid crystal polarizing film.

[0093] The liquid crystal polarizing film forming composition may contain additives other than photosensitizers and leveling agents. Examples of other additives include antioxidants, mold release agents, stabilizers, colorants such as bluing agents, flame retardants, and lubricants. When the liquid crystal polarizing film forming composition contains other additives, the content of the other additives is preferably more than 0% and 20% by mass or less, and more preferably more than 0% and 10% by mass or less, relative to the solid content of the liquid crystal polarizing film forming composition.

[0094] A liquid crystal polarizing film forming composition can be prepared by conventionally known methods for preparing liquid crystal polarizing film forming compositions. Typically, it can be prepared by mixing and stirring a polymerizable liquid crystal compound and a dichroic dye, and optionally a polymerization initiator and the above-mentioned additives. Furthermore, since compounds exhibiting smectic liquid crystal properties generally have high viscosity, viscosity adjustment may be performed by adding a solvent to the liquid crystal polarizing film forming composition to improve its applicability and facilitate the formation of a liquid crystal polarizing film.

[0095] The solvent used in the composition for forming liquid crystal polarizing films can be appropriately selected depending on the solubility of the polymerizable liquid crystal compound and dichroic dye used. Specifically, examples include alcohol solvents such as water, methanol, ethanol, ethylene glycol, isopropyl alcohol, propylene glycol, methyl cellosolve, butyl cellosolve, and propylene glycol monomethyl ether; ester solvents such as ethyl acetate, butyl acetate, ethylene glycol methyl ether acetate, γ-butyrolactone, propylene glycol methyl ether acetate, and ethyl lactate; ketone solvents such as acetone, methyl ethyl ketone, cyclopentanone, cyclohexanone, methyl amyl ketone, and methyl isobutyl ketone; aliphatic hydrocarbon solvents such as pentane, hexane, and heptane; aromatic hydrocarbon solvents such as toluene and xylene; nitrile solvents such as acetonitrile; ether solvents such as tetrahydrofuran and dimethoxyethane; and chlorinated hydrocarbon solvents such as chloroform and chlorobenzene. These solvents can be used individually or in combination of two or more. The solvent content is preferably 100 to 1900 parts by mass, more preferably 150 to 900 parts by mass, and even more preferably 180 to 600 parts by mass, per 100 parts by mass of solid content of the liquid crystal polarizing film forming composition.

[0096] In the optical laminate of the present invention, the liquid crystal polarizing film is preferably a liquid crystal polarizing film with a high degree of orientation order. A liquid crystal polarizing film with a high degree of orientation order yields Bragg peaks originating from higher-order structures such as the hexatic phase and the crystal phase in X-ray diffraction measurements. A Bragg peak refers to a peak originating from the plane-periodic structure of molecular orientation. Therefore, it is preferable that the liquid crystal polarizing film constituting the optical laminate of the present invention exhibits a Bragg peak in X-ray diffraction measurements. That is, in the liquid crystal polarizing film constituting the optical laminate of the present invention, it is preferable that the polymerizable liquid crystal compound or its polymer is oriented such that the liquid crystal polarizing film exhibits a Bragg peak in X-ray diffraction measurements, and it is more preferable that the molecules of the polymerizable liquid crystal compound are oriented in a "horizontal orientation" in the direction that absorbs light. In the present invention, a liquid crystal polarizing film with a plane-periodic spacing of molecular orientation of 3.0 to 6.0 Å is preferred. A high degree of orientation order that exhibits a Bragg peak can be achieved by controlling the type of polymerizable liquid crystal compound used, the type and amount of dichroic dye, and the type and amount of polymerization initiator.

[0097] In one embodiment of the present invention, a liquid crystal polarizing film can be obtained by a method comprising: forming a coating film of a liquid crystal polarizing film forming composition on a release film or an adjacent layer or film (for example, an alignment film or a hard coat layer, etc.) in an optical laminate with respect to the liquid crystal polarizing film; removing a solvent from the coating film; raising the temperature to a temperature above which the polymerizable liquid crystal compound undergoes a phase transition to the liquid phase, and then lowering the temperature to cause the polymerizable liquid crystal compound to undergo a phase transition to the smectic phase; and polymerizing the polymerizable liquid crystal compound while retaining the smectic phase.

[0098] As a method for applying the liquid crystal polarizing film-forming composition to a release film or the like, the same method as the method for applying the adhesive composition described above can be used. The contact surface of the release film or the like that comes into contact with the coated film of the liquid crystal polarizing film-forming composition may be subjected to surface treatment such as corona treatment or plasma treatment.

[0099] Next, a dried coating film is formed by removing the solvent by drying or other means under conditions in which the polymerizable liquid crystal compound contained in the coating film obtained from the liquid crystal polarizing film forming composition does not polymerize. Examples of drying methods include natural drying, forced-air drying, heat drying, and reduced-pressure drying.

[0100] Furthermore, in order to cause the polymerizable liquid crystal compound to undergo a phase transition to the liquid phase, the temperature is raised to above the temperature at which the polymerizable liquid crystal compound undergoes a phase transition to the liquid phase, and then the temperature is lowered to cause the polymerizable liquid crystal compound to undergo a phase transition to the smectic phase (smectic liquid crystal state). This phase transition may be performed after the removal of the solvent in the coating film, or it may be performed simultaneously with the removal of the solvent.

[0101] A liquid crystal polarizing film is formed as a cured layer of a liquid crystal polarizing film-forming composition by polymerizing a polymerizable liquid crystal compound while maintaining its smectic liquid crystal state. Photopolymerization is preferred as the polymerization method. In photopolymerization, the light irradiated onto the dry coating film is appropriately selected depending on the type of polymerizable liquid crystal compound contained in the dry coating film (particularly the type of polymerizable group the polymerizable liquid crystal compound possesses), the type of polymerization initiator, and their amounts. Specific examples include one or more active energy rays or active electron beams selected from the group consisting of visible light, ultraviolet light, infrared light, X-rays, alpha rays, beta rays, and gamma rays. Among these, ultraviolet light is preferred because it allows control of the polymerization reaction and allows the use of photopolymerization equipment that is widely used in this field. It is preferable to select the types of polymerizable liquid crystal compounds and polymerization initiators contained in the liquid crystal polarizing film-forming composition so that photopolymerization is possible using ultraviolet light. Furthermore, the polymerization temperature can also be controlled by irradiating the dry coating film with light while cooling it with an appropriate cooling means during polymerization. During photopolymerization, patterned liquid crystal polarizing films can also be obtained by performing masking and development.

[0102] Examples of the light sources for the activated energy rays include low-pressure mercury lamps, medium-pressure mercury lamps, high-pressure mercury lamps, ultra-high-pressure mercury lamps, xenon lamps, halogen lamps, carbon arc lamps, tungsten lamps, gallium lamps, excimer lasers, LED light sources emitting light in the wavelength range of 380-440 nm, chemical lamps, black light lamps, microwave-excited mercury lamps, metal halide lamps, and the like.

[0103] The UV irradiation intensity is typically 10-3,000 mW / cm². 2 The ultraviolet irradiation intensity is preferably in the wavelength range effective for activating the polymerization initiator. The irradiation time is usually 0.1 seconds to 10 minutes, preferably 1 second to 5 minutes, more preferably 5 seconds to 3 minutes, and even more preferably 10 seconds to 1 minute. When irradiation is performed once or multiple times at such ultraviolet irradiation intensity, the accumulated light amount is 10 to 3,000 mJ / cm². 2 Preferably 50 to 2,000 mJ / cm² 2 More preferably 100-1,000 mJ / cm² 2 That is the case.

[0104] By photopolymerization, the polymerizable liquid crystal compound polymerizes while maintaining the liquid crystal state of the smectic phase, preferably a higher-order smectic phase, thereby forming a liquid crystal polarizing film. The liquid crystal polarizing film obtained by polymerizing the polymerizable liquid crystal compound while maintaining the liquid crystal state of the smectic phase has the advantage of higher polarization performance compared to conventional host-guest type polarizing films, i.e., liquid crystal polarizing films consisting of a liquid crystal state of the nematic phase, due to the action of the dichroic dye. Furthermore, it also has the advantage of superior strength compared to films coated only with dichroic dyes or lyotropic liquid crystals.

[0105] The thickness of the liquid crystal polarizing film can be appropriately selected depending on the applicable display device, preferably a film of 0.1 to 5 μm, more preferably 0.3 to 4 μm, and even more preferably 0.5 to 3 μm. If the film thickness of the liquid crystal polarizing film is above the lower limit, it is possible to prevent the loss of necessary light absorption, and if it is below the upper limit, it is possible to suppress the occurrence of orientation defects due to a decrease in the orientation rule force by the alignment film.

[0106] (Orientation film) The polarizing film in the present invention may include an alignment film adjacent to the liquid crystal polarizing film. The alignment film has an alignment-regulating force that causes the polymerizable liquid crystal compound contained in the liquid crystal polarizing film forming composition to be liquid crystal oriented in a desired direction. From the viewpoint of this alignment-regulating force, if the polarizing film includes an alignment film, it is preferable to apply the liquid crystal polarizing film forming composition on top of the alignment film. The alignment film is preferably solvent-resistant, not dissolved by the application of the polarizing film-forming composition, and also heat-resistant in the removal of solvents and in heat treatment for the alignment of polymerizable liquid crystal compounds. From the viewpoint of adhesion to adjacent layers or films, the alignment film is preferably a cured product of the alignment film-forming composition containing a (meth)acrylic compound. Furthermore, from the viewpoint of improving adhesion and heat resistance, the alignment film is preferably a photo-alignment film formed by curing the alignment film-forming composition with polarization (preferably polarized UV).

[0107] The (meth)acrylic compound refers to a compound having at least one (meth)acrylic group, and may be a monomer, oligomer, or polymer. If it is an oligomer or polymer, the double bonds of the (meth)acrylic group may be polymerized. The (meth)acrylic compound included in the aligning film-forming composition preferably has a photoreactive group in addition to the (meth)acrylic group.

[0108] A photoreactive group is a group that generates liquid crystal alignment ability upon light irradiation. Specifically, this includes groups involved in photoreactions that are the origin of liquid crystal alignment ability, such as molecular orientation induction or isomerization reactions, dimerization reactions, photocrosslinking reactions, or photodegradation reactions, which are induced by light irradiation. Among these, groups involved in dimerization reactions or photocrosslinking reactions are preferred because they exhibit excellent orientation properties. As photoreactive groups, groups having unsaturated bonds, especially double bonds, are preferred, and groups having at least one selected from the group consisting of carbon-carbon double bonds (C=C bonds), carbon-nitrogen double bonds (C=N bonds), nitrogen-nitrogen double bonds (N=N bonds), and carbon-oxygen double bonds (C=O bonds) are particularly preferred.

[0109] Examples of photoreactive groups having a C=C bond include vinyl groups, polyene groups, stilbene groups, stilbazole groups, stilbazolium groups, chalcone groups, and cinnamoyl groups. Examples of photoreactive groups having a C=N bond include groups having structures such as aromatic Schiff bases and aromatic hydrazones. Examples of photoreactive groups having an N=N bond include azobenzene groups, azonaphthalene groups, aromatic heterocyclic azo groups, bisazo groups, formazan groups, and groups having an azoxybenzene structure. Examples of photoreactive groups having a C=O bond include benzophenone groups, coumarin groups, anthraquinone groups, and maleimide groups. These groups may have substituents such as alkyl groups, alkoxy groups, aryl groups, allyloxy groups, cyano groups, alkoxycarbonyl groups, hydroxyl groups, sulfonic acid groups, and halogenated alkyl groups.

[0110] Among these, photoreactive groups involved in the photodimerization reaction are preferred, and cinnamoyl groups and chalcone groups are preferred because they allow for relatively little polarized irradiation required for photo-alignment, and make it easier to obtain a photo-alignment film with excellent thermal stability and chronological stability. As for the (meth)acrylic oligomer or polymer contained in the composition for forming the photo-alignment film (composition for forming the photo-alignment film), those having cinnamoyl groups such that the terminal portion of the oligomer or polymer side chain has a cinnamic acid structure are particularly preferred.

[0111] In one embodiment of the present invention, a photo-alignment film can be obtained by applying a photo-alignment film-forming composition containing a (meth)acrylic compound and a solvent onto an adjacent layer (e.g., a hard coat layer) on the opposite side of the liquid crystal polarizing film, and irradiating it with polarized light (preferably polarized UV). The solvent included in the photo-alignment film-forming composition is the same as the solvent previously exemplified as a solvent that can be used when forming a liquid crystal polarizing film, and can be appropriately selected depending on the solubility of the (meth)acrylic compound.

[0112] The content of the (meth)acrylic compound in the photo-alignment film-forming composition can be appropriately adjusted depending on the type of (meth)acrylic compound and the desired thickness of the photo-alignment film, but it is preferably at least 0.2% by mass, and more preferably in the range of 0.3 to 10% by mass, relative to the mass of the photo-alignment film-forming composition. The photo-alignment film-forming composition may also contain polymer materials such as polyvinyl alcohol or polyimide, or photosensitizers, as long as the properties of the photo-alignment film are not significantly impaired.

[0113] Methods for applying the photo-alignment film-forming composition onto an adjacent layer opposite to the liquid crystal polarizing film, and methods for removing the solvent from the applied photo-alignment film-forming composition, include the method of applying an adhesive composition and the method for removing the solvent from the liquid crystal polarizing film, as exemplified above.

[0114] Polarized light irradiation can be performed by directly irradiating a photo-alignment film-forming composition coated on an adjacent layer opposite to the liquid crystal polarizing film with polarized UV light after removing the solvent, or by irradiating polarized light from the adjacent layer opposite to the liquid crystal polarizing film and transmitting the polarized light. Furthermore, it is particularly preferable that the polarized light is substantially parallel light. The wavelength of the polarized light to be irradiated should be in the wavelength range in which the photoreactive groups and / or (meth)acrylic groups of the (meth)acrylic compound can absorb light energy. Specifically, UV (ultraviolet) light in the wavelength range of 250 to 400 nm is particularly preferred. Examples of light sources used for the polarized light irradiation include xenon lamps, high-pressure mercury lamps, ultra-high-pressure mercury lamps, metal halide lamps, and ultraviolet light lasers such as KrF and ArF, with high-pressure mercury lamps, ultra-high-pressure mercury lamps and metal halide lamps being more preferred. Among these, high-pressure mercury lamps, ultra-high-pressure mercury lamps and metal halide lamps are preferred because they have a high emission intensity of ultraviolet light at a wavelength of 313 nm. Polarized UV light can be emitted by passing light from the aforementioned light source through a suitable polarizer. Such polarizers can include polarizing filters, polarizing prisms such as Grant-Thomson or Grant-Taylor, or wire grid type polarizers.

[0115] Furthermore, by applying masking when irradiating with polarized light, it is possible to form multiple regions (patterns) with different liquid crystal orientation directions.

[0116] The thickness of the alignment film is preferably 10 to 5000 nm, more preferably 10 to 1000 nm, and even more preferably 30 to 300 nm. When the thickness of the alignment film is within the above range, it is possible to exhibit alignment order while maintaining good adhesion with adjacent layers, and a liquid crystal polarizing film can be formed with high alignment order.

[0117] <Retardation film> In one embodiment of the present invention, the optical laminate includes a phase difference film adjacent to the polarizing film of the adhesive layer, and the phase difference film includes a cured layer of a polymerizable liquid crystal composition containing a polymerizable liquid crystal compound. The phase difference film consists of a cured layer of a polymerizable liquid crystal composition containing a polymerizable liquid crystal compound (sometimes referred to as "liquid crystal phase difference film" in this specification), or consists of a liquid crystal phase difference film and an alignment film adjacent to the liquid crystal phase difference film. When the phase difference film consists of a liquid crystal phase difference film and an alignment film adjacent to the liquid crystal phase difference film, in the optical laminate, the liquid crystal phase difference film may be located on the adhesive layer side, or the alignment film may be located on the adhesive layer side. From the viewpoint of maintaining the function of the phase difference film as a λ / 4 wave plate with higher precision in a high-temperature environment, it is preferable that the alignment film be located on the adhesive layer side.

[0118] As described above, in the present invention, because the composition forming the adhesive layer contained in the optical laminate contains specific compounds (A) to (D), the adhesive layer can have good flexibility and good adhesion to adjacent layers. As a result, the adhesive layer can adhere well to adjacent layers. Therefore, in this embodiment in which the optical laminate contains a phase difference film adjacent to the polarizing film on the opposite side of the adhesive layer, the adhesive layer can adhere well to the phase difference film, thereby providing an optical laminate (circular polarizer) with excellent durability.

[0119] Furthermore, in general, it is preferable that the difference in refractive index between the layers contained in an optical laminate is small. The inventors have also found that by selecting specific compounds (A) to (D) as components in the composition that forms the adhesive layer contained in the optical laminate of the present invention, the difference in refractive index between the adhesive layer and the polarizing film adjacent to it, and the phase difference film when adjacent, can be reduced.

[0120] In this embodiment, in an optical laminate, a phase difference film is adjacent to the polarizing film of the adhesive layer on the opposite side. When the in-plane average refractive index of the polarizing film is n1, the in-plane average refractive index of the adhesive layer is n2, and the in-plane average refractive index of the phase difference film is n3, the optical laminate is given by the following formula (1): |(n1×n3) 1 / 2 -n²| ≤ 0.070 (1) It is preferable that the following conditions are met. The value on the left side of equation (1) indicates that the difference in refractive index between the polarizing film, adhesive layer, and phase difference film included in the optical laminate is small. The smaller this difference in refractive index, the more light reflection in the optical laminate can be suppressed, and as a result, visibility can be improved when the optical laminate is mounted on an image display panel or the like. The difference in refractive index is more preferably 0.065 or less, even more preferably 0.060 or less, particularly preferably less than 0.060, and may be, for example, 0.055 or less, and is usually 0.001 or more. When the polarizing film consists of a liquid crystal polarizing film and an alignment film, the in-plane average refractive index n1 means the in-plane average refractive index measured for the liquid crystal polarizing film alone. On the other hand, when the phase difference film consists of a liquid crystal phase difference film and an alignment film, the in-plane average refractive index n3 means the in-plane average refractive index measured for the liquid crystal phase difference film and the alignment film together.

[0121] The difference in refractive index can be controlled by the types of components constituting the polarizing film, adhesive layer, and phase difference film, their combinations, and their mixing ratios.

[0122] In the above embodiment of the present invention, the in-plane average refractive index n1 of the polarizing film is preferably 1.49 to 1.60, more preferably 1.52 to 1.58. When the in-plane average refractive index n1 of the polarizing film is within the above range, light reflection at the interface between the polarizing film and the adhesive layer can be suppressed. The in-plane average refractive index n1 of the polarizing film can be controlled by the type of components constituting the polarizing film, their combination and mixing ratio, orientation state, etc.

[0123] In the above embodiment of the present invention, the in-plane average refractive index n2 of the adhesive layer is preferably 1.45 to 1.58, more preferably 1.50 to 1.53. When the in-plane average refractive index n2 of the adhesive layer is within the above range, light reflection at the interface with the polarizing film can be suppressed, and light reflection at the interface with the phase difference film can also be suppressed. The in-plane average refractive index n2 of the adhesive layer can be controlled by the type of components constituting the adhesive layer, their combination and mixing ratio, etc.

[0124] In the above embodiment of the present invention, the in-plane average refractive index n3 of the phase difference film is preferably 1.50 to 1.70, more preferably 1.55 to 1.65. When the in-plane average refractive index n3 of the phase difference film is within the above range, light reflection at the interface with the adhesive layer can be suppressed. The in-plane average refractive index n3 of the phase difference film can be controlled by the type of polymerizable liquid crystal compound constituting the phase difference film, its combination and mixing ratio, orientation state, etc.

[0125] In the present invention, the in-plane average refractive index of the polarizing film, adhesive layer, and phase difference film is the refractive index at a wavelength of 589 nm, and can be measured using an Abbe refractometer or a KOBRA-WR (manufactured by Oji Instruments Co., Ltd.). Specifically, it can be measured, for example, according to the method described in the examples below.

[0126] In the present invention, the liquid crystal phase difference film can be formed by polymerizing a polymerizable liquid crystal compound (hereinafter also referred to as "polymerizable liquid crystal compound (B)") contained in the phase difference film forming composition, and is a film cured in a state in which the polymerizable liquid crystal compound is oriented. For the optical laminate of the present invention to function as a circular polarizer, it is preferable to include a liquid crystal phase difference film having a λ / 4 wave plate function (i.e., a π / 2 phase difference function) as the liquid crystal phase difference film. If the liquid crystal phase difference film has a λ / 4 wave plate function over the entire visible light range, a high level of anti-reflection function can be achieved. A liquid crystal phase difference film having a λ / 4 wave plate function may be, for example, a "horizontally oriented liquid crystal cured film" in which the polymerizable liquid crystal compound (B) is cured in a state in which it is oriented horizontally with respect to the phase difference film plane. In this case, if the polymerizable liquid crystal compound (B) is a rod-shaped liquid crystal, it may be a positive A plate, and if the polymerizable liquid crystal compound (B) is a disc-shaped liquid crystal, it may be a negative A plate.

[0127] The optical laminate of the present invention preferably includes a liquid crystal phase difference film that satisfies the optical properties shown in the following formula (2) when the in-plane phase difference value with respect to light of wavelength λnm is R(λ). In one embodiment of the present invention, it is more preferable to include a liquid crystal phase difference film that satisfies the optical properties shown in the following formulas (2), (3), and (4). 100nm <Re(550)<170nm (2) (In the formula, Re(550) represents the in-plane phase difference value (in-plane retardation) for light with a wavelength of 550 nm.) Re(450) / Re(550)≦1.0 (3) 1.00 ≤ Re(650) / Re(550) (4) (In the formula, Re(450) represents the in-plane phase difference value for light with a wavelength of 450 nm, Re(550) represents the in-plane phase difference value for light with a wavelength of 550 nm, and Re(650) represents the in-plane phase difference value for light with a wavelength of 650 nm.)

[0128] If the in-plane phase difference Re(550) of the liquid crystal phase difference film is within the range of equation (2), the phase difference film functions as a λ / 4 wave plate, and the effect of improving the front reflected hue (effect of suppressing coloration) when an optical laminate (circular polarizer) containing the phase difference film is applied to an organic EL display device, etc., is enhanced. Furthermore, if the liquid crystal phase difference film satisfies the above equations (3) and (4), it exhibits so-called inverse wavelength dispersion, where the in-plane phase difference value at short wavelengths is smaller than the in-plane phase difference value at long wavelengths. An optical laminate (circular polarizer) having such a liquid crystal phase difference film has an excellent effect of suppressing light leakage on the short wavelength side and tends to have excellent front hue when incorporated into an organic EL display device, etc. From the viewpoint of improving inverse wavelength dispersion and further enhancing the effect of improving the reflected hue in the front direction, Re(450) / Re(550) is preferably 0.7 to 1.0, more preferably 0.80 to 0.95, even more preferably 0.80 to 0.92, and particularly preferably 0.82 to 0.88. Also, Re(650) / Re(550) is preferably 1.01 or higher, more preferably 1.02 or higher. These values ​​can be arbitrarily controlled by adjusting the mixing ratio of polymerizable liquid crystal compound (B) and the stacking angle and phase difference value of the multiple phase difference films.

[0129] The above in-plane phase difference value can be adjusted by the film thickness d of the liquid crystal phase difference film. The in-plane phase difference value is determined by the formula: Re(λ)=(nx(λ)-ny(λ))×d [wherein nx(λ) represents the principal refractive index at wavelength λnm in the plane of the liquid crystal phase difference film, ny(λ) represents the refractive index at wavelength λnm in the direction perpendicular to the direction of nx in the same plane as nx, and d represents the film thickness of the liquid crystal phase difference film]. Therefore, to obtain the desired in-plane phase difference value (Re(λ): in-plane phase difference value of the phase difference film at wavelength λ(nm)), the three-dimensional refractive index and film thickness d should be adjusted.

[0130] In the optical layered body of the present invention, the number of retardation films may be one, or two or more. Specifically, it is preferable to include a retardation film having a λ / 4 wavelength plate function, particularly a retardation film having a reverse wavelength dispersion λ / 4 wavelength plate function, or it is preferable to combine two or more types of retardation films with different orientations. For example, a combination of a retardation film having a λ / 2 wavelength plate function (that is, a π retardation function) and a retardation film having a λ / 4 wavelength plate function (that is, a π / 2 retardation function) may be used. Furthermore, for example, in addition to the retardation film having a λ / 4 wavelength plate function, a retardation film that is a positive C-plate (nx≈ny<nz) may be included. The liquid crystal retardation film that is a positive C-plate is usually a "vertically aligned liquid crystal cured film" obtained by curing a polymerizable liquid crystal compound (B) in a state of being aligned in the direction perpendicular to the plane of the retardation film. By including a retardation film having a 1 / 4 wavelength plate function and a retardation film that is a positive C-plate in combination, when the optical layered body is applied to an organic EL display device or the like, improvement in the oblique reflection hue can be expected in addition to the improvement in the front reflection hue. Each of the liquid crystal retardation films may have a tilt alignment, or may form a cholesteric alignment state. When the optical layered body includes two or more retardation films, it is preferable that at least one retardation film is present adjacent to the adhesive layer, and it is more preferable that the retardation film having a λ / 4 wavelength plate function is present adjacent to the adhesive layer. In an embodiment including a plurality of retardation films, a retardation film other than the retardation film adjacent to the adhesive layer may, for example, be bonded to another layer with a conventionally known pressure-sensitive adhesive or adhesive, or may be a layer obtained by directly applying a composition for forming a retardation film for forming the retardation film onto another layer for lamination.

[0131] The polymerizable liquid crystal compound (B) for forming the phase difference film can be appropriately selected from polymerizable liquid crystal compounds conventionally known in the field of phase difference plates, depending on the desired optical properties. In the present invention, the polymerizable liquid crystal compound (B) can be classified, for example, into rod-shaped type (rod-shaped liquid crystal compound) and disc-shaped type (disc-shaped liquid crystal compound, discotic liquid crystal compound) based on its shape, and either type of liquid crystal compound can be used. Furthermore, two or more rod-shaped liquid crystal compounds, two or more disc-shaped liquid crystal compounds, or a mixture of rod-shaped and disc-shaped liquid crystal compounds may be used.

[0132] Polymerizable liquid crystal compound (B) is a compound having at least one polymerizable group and possessing liquid crystal properties. Generally, polymerizable liquid crystal compounds (B) include polymerizable liquid crystal compounds that exhibit positive wavelength dispersibility and polymerizable liquid crystal compounds that exhibit inverse wavelength dispersibility, obtained by polymerizing the polymerizable liquid crystal compound alone in a specific orientation (cured product). In the present invention, only one type of polymerizable liquid crystal compound may be used, or both types may be mixed and used. Furthermore, for example, if the optical laminate includes a phase difference film having a λ / 4 wave plate function and a phase difference film that is a positive C plate, the polymerizable liquid crystal compounds constituting these may be the same or different.

[0133] In the present invention, the polymerizable group of the polymerizable liquid crystal compound (B) that forms the phase difference film is preferably a photopolymerizable group, and examples of polymerizable groups include those exemplified as polymerizable groups of the polymerizable liquid crystal compound (A) that can constitute a liquid crystal polarizing film. Among these, acryloyloxy groups, methacryloyloxy groups, vinyloxy groups, oxyranyl groups, and oxetanyl groups are more preferred, and acryloyloxy groups or methacryloyloxy groups are even more preferred. The liquid crystalline properties may be either thermotropic or lyotropic liquid crystal, but thermotropic liquid crystal is preferred because it allows for precise control of the film thickness. Furthermore, the phase order structure in the thermotropic liquid crystal may be either nematic or smectic liquid crystal. As the polymerizable liquid crystal compound (B), only one type may be used, or two or more types may be used in combination.

[0134] When the optical laminate of the present invention includes a phase difference film having a λ / 4 wave plate function, the polymerizable liquid crystal compound (B) that forms the phase difference film having a λ / 4 wave plate function preferably includes a polymerizable liquid crystal compound having a T-shaped or H-shaped mesogenic structure that further exhibits birefringence in the direction perpendicular to the molecular long axis, from the viewpoint of exhibiting inverse wavelength dispersion, and more preferably includes a T-shaped polymerizable liquid crystal compound from the viewpoint of obtaining stronger dispersion.

[0135] A polymerizable liquid crystal compound having a T-shaped liquid crystal structure is, for example, the following formula (B1): P 1 -E 1 -( B 1 -G 1 ) k -L 1 -Ar-L 2 -(G 2 -B 2 ) l -E 2 -P 2 (B1) Examples include compounds represented by (hereinafter also referred to as "polymerizable liquid crystal compounds (B1)").

[0136] In formula (B1), Ar represents a divalent aromatic group which may have substituents. Preferably, the divalent aromatic group contains at least one of nitrogen, oxygen, and sulfur atoms. If the divalent group Ar contains two or more aromatic groups, the two or more aromatic groups may be linked to each other by single bonds, divalent bonding groups such as -CO-O- and -O-. G 1 and G 2 Each of these independently represents a divalent aromatic group or a divalent alicyclic hydrocarbon group. Here, the hydrogen atoms contained in the divalent aromatic group or divalent alicyclic hydrocarbon group may be substituted with halogen atoms, C1-C4 alkyl groups, C1-C4 fluoroalkyl groups, C1-C4 alkoxy groups, cyano groups, or nitro groups, and the carbon atoms constituting the divalent aromatic group or divalent alicyclic hydrocarbon group may be substituted with oxygen atoms, sulfur atoms, or nitrogen atoms. L1 , L 2 、 B 1 and B 2 Each of these is independently a single bond or a divalent linking group. k and l each represent integers from 0 to 3 independently, satisfying the relationship 1 ≤ k + l. Here, if 2 ≤ k + l, then B 1 and B 2 , G 1 and G 2 These elements may be identical to each other, or they may be different. E 1 and E 2 Each of these independently represents an alkanediyl group having 1 to 17 carbon atoms, where the hydrogen atoms in the alkanediyl group may be substituted with halogen atoms, and the -CH2- groups in the alkanediyl group may be substituted with -O-, -S-, or -COO-, and if there are multiple -O-, -S-, or -COO- groups, they are not adjacent to each other. 1 and P 2 Each of these independently represents a polymerizable group or a hydrogen atom, and at least one of them is a polymerizable group.

[0137] G 1 and G 2 Each of these is independently preferably a 1,4-phenylenediyl group which may be substituted with at least one substituent selected from the group consisting of a halogen atom and an alkyl group having 1 to 4 carbon atoms, or a 1,4-cyclohexanediyl group which may be substituted with at least one substituent selected from the group consisting of a halogen atom and an alkyl group having 1 to 4 carbon atoms, more preferably a methyl-substituted 1,4-phenylenediyl group, an unsubstituted 1,4-phenylenediyl group, or an unsubstituted 1,4-trans-cyclohexanediyl group, and particularly preferably an unsubstituted 1,4-phenylenediyl group or an unsubstituted 1,4-trans-cyclohexandiyl group. Also, there are multiple G 1 and G 2 Preferably, at least one of them is a divalent alicyclic hydrocarbon group, and L 1 or L 2 G that joins 1and G 2 It is more preferable that at least one of these is a divalent alicyclic hydrocarbon group.

[0138] L 1 and L 2 Each of these is independently, preferably a single bond, an alkylene group having 1 to 4 carbon atoms, -O-, -S-, -R a1 Ure a2 -, -R a3 COOR a4 -, -R a5 OCOR a6 -, -R a7 OC=OOR a8 -, -N=N-, -CR c =CR d -, or -C≡C-. Here, R a1 ~R a8 Each of these independently represents a single bond or an alkylene group with 1 to 4 carbon atoms, R c and R d L represents an alkyl group with 1 to 4 carbon atoms or a hydrogen atom. 1 and L 2 Each is independently, more preferably a single bond, -OR a2-1 -, -CH2-, -CH2CH2-, -COOR a4-1 -, or -OCOR a6-1 - is the case here R a2-1 , R a4-1 , R a6-1 Each of these independently represents either a single bond, -CH2-, or -CH2CH2-. 1 and L 2 Each of these is independently, and more preferably, a single bond, -O-, -CH2CH2-, -COO-, -COOCH2CH2-, or -OCO-.

[0139] B 1 and B 2 Each of these is independently, preferably a single bond, an alkylene group having 1 to 4 carbon atoms, -O-, -S-, -R a9 Ure a10 -, -R a11 COOR a12 -, -R a13 OCOR a14 -, or R a15 OC=OORa16 - is the case here R a9 ~R a16 Each of these independently represents a single bond or an alkylene group with 1 to 4 carbon atoms. 1 and B 2 Each is independently, more preferably a single bond, -OR a10-1 -, -CH2-, -CH2CH2-, -COOR a12-1 -, or -OCOR a14-1 - is the case here R a10-1 , R a12-1 , R a14-1 Each of these independently represents either a single bond, -CH2-, or -CH2CH2-. 1 and B 2 Each of these is independently, and more preferably, a single bond, -O-, -CH2CH2-, -COO-, -COOCH2CH2-, -OCO-, or -OCOCH2CH2-.

[0140] From the viewpoint of exhibiting inverse wavelength dispersion, k and l are preferably in the range of 2 ≤ k + l ≤ 6, preferably k + l = 4, and more preferably k = 2 and l = 2. A symmetric structure is preferred when k = 2 and l = 2.

[0141] E 1 and E 2 Each of these groups is independently preferably an alkanediyl group having 1 to 17 carbon atoms, and more preferably an alkanediyl group having 4 to 12 carbon atoms.

[0142] P 1 or P 2 Examples of polymerizable groups represented by include epoxy groups, vinyl groups, vinyloxy groups, 1-chlorovinyl groups, isopropenyl groups, 4-vinylphenyl groups, acryloyloxy groups, methacryloyloxy groups, oxyranyl groups, and oxetanyl groups. Among these, acryloyloxy groups, methacryloyloxy groups, vinyloxy groups, oxyranyl groups, and oxetanyl groups are preferred, with acryloyloxy groups being more preferred.

[0143] Ar preferably has at least one selected from the group consisting of an aromatic hydrocarbon ring which may have a substituent, an aromatic heterocyclic ring which may have a substituent, and an electron-withdrawing group. Examples of the aromatic hydrocarbon ring include a benzene ring, a naphthalene ring, an anthracene ring and the like, and a benzene ring and a naphthalene ring are preferred. Examples of the aromatic heterocyclic ring include a furan ring, a benzofuran ring, a pyrrole ring, an indole ring, a thiophene ring, a benzothiophene ring, a pyridine ring, a pyrazine ring, a pyrimidine ring, a triazole ring, a triazine ring, a pyrroline ring, an imidazole ring, a pyrazole ring, a thiazole ring, a benzothiazole ring, a thienothiazole ring, an oxazole ring, a benzoxazole ring, a phenanthroline ring and the like. Among these, it preferably has a thiazole ring, a benzothiazole ring or a benzofuran ring, and more preferably has a benzothiazole group. When Ar contains a nitrogen atom, the nitrogen atom preferably has a π electron.

[0144] In formula (B1), the total number N of π electrons contained in the divalent aromatic group represented by Ar π is preferably 8 or more, more preferably 10 or more, still more preferably 14 or more, and particularly preferably 16 or more. Also, it is preferably 36 or less, more preferably 32 or less, still more preferably 26 or less, and particularly preferably 24 or less.

[0145] Preferable examples of the aromatic group represented by Ar include the following groups.

[0146]

Chemical Formula

[0147] In formula (Ar-1) to formula (Ar-23), the * mark represents a linking moiety, and Z 0 , Z 1 and Z 2Each of these independently represents a hydrogen atom, a halogen atom, a C1-C12 alkyl group, a cyano group, a nitro group, a C1-C12 alkylsulfinyl group, a C1-C12 alkylsulfonyl group, a carboxyl group, a C1-C12 fluoroalkyl group, a C1-C6 alkoxy group, a C1-C12 alkylthio group, a C1-C12 N-alkylamino group, a C2-C12 N,N-dialkylamino group, a C1-C12 N-alkylsulfamoyl group, or a C2-C12 N,N-dialkylsulfamoyl group.

[0148] Q 1 , and Q 2 These are, independently, -CR 2’ R 3’ -, -S-, -NH-, -NR 2’ - represents -CO- or -O-, R 2’ and R 3’ Each of these independently represents either a hydrogen atom or an alkyl group having 1 to 4 carbon atoms.

[0149] J 1 , and J 2 Each of these independently represents either a carbon atom or a nitrogen atom.

[0150] Y 1 , and Y 2 Each of these independently represents an optionally substituted aromatic hydrocarbon group or an aromatic heterocyclic group.

[0151] W 1 and W 2 Each of these independently represents a hydrogen atom, a cyano group, a methyl group, or a halogen atom, and m represents an integer from 0 to 6.

[0152] Y 1 , and Y 2Examples of aromatic hydrocarbon groups in this context include C6-C20 aromatic hydrocarbon groups such as phenyl, naphthyl, anthuryl, phenanthuryl, and biphenyl groups, with phenyl and naphthyl groups being preferred and phenyl groups being more preferred. Examples of aromatic heterocyclic groups include C4-C20 aromatic heterocyclic groups containing at least one heteroatom such as a nitrogen atom, oxygen atom, or sulfur atom, such as furyl, pyrrolyl, thienyl, pyridinyl, thiazolyl, and benzothiazolyl groups, with furyl, thienyl, pyridinyl, thiazolyl, and benzothiazolyl groups being preferred.

[0153] Y 1 , and Y 2 Each of these may independently be a substituted polycyclic aromatic hydrocarbon group or a polycyclic aromatic heterocyclic group. A polycyclic aromatic hydrocarbon group refers to a fused polycyclic aromatic hydrocarbon group or a group derived from an aromatic ring assembly. A polycyclic aromatic heterocyclic group refers to a fused polycyclic aromatic heterocyclic group or a group derived from an aromatic ring assembly.

[0154] Z 0 , Z 1 and Z 2 Each of these is preferably independently a hydrogen atom, a halogen atom, a C1-C12 alkyl group, a cyano group, a nitro group, or a C1-C12 alkoxy group, Z 0 A hydrogen atom, an alkyl group having 1 to 12 carbon atoms, and a cyano group are more preferably Z 1 and Z 2 Hydrogen atoms, fluorine atoms, chlorine atoms, methyl groups, and cyano groups are more preferred.

[0155] Q 1 , and Q 2 -NH-, -S-, -NR 2’ -, -O- is preferred, R 2’ A hydrogen atom is preferred. Among these, -S-, -O-, and -NH- are particularly preferred.

[0156] Among formulas (Ar-1) to (Ar-23), formulas (Ar-6) and (Ar-7) are preferred from the viewpoint of molecular stability. In equations (Ar-17) to (Ar-23), Y 1 This is the nitrogen atom and Z to which it is bonded. 0 It may also form an aromatic heterocyclic group. Examples of aromatic heterocyclic groups that Ar may have include those mentioned above, such as a pyrrole ring, imidazole ring, pyrroline ring, pyridine ring, pyrazine ring, pyrimidine ring, indole ring, quinoline ring, isoquinoline ring, purine ring, pyrrolidine ring, etc. This aromatic heterocyclic group may have substituents. Also, Y 1 This is the nitrogen atom and Z to which it is bonded. 0 In addition, the aforementioned substituted polycyclic aromatic hydrocarbon groups or polycyclic aromatic heterocyclic groups may also be used. Examples include benzofuran rings, benzothiazole rings, and benzoxazole rings.

[0157] Polymerizable liquid crystal compound (B1) can be produced, for example, by the method described in Japanese Patent Application Publication No. 2010-31223.

[0158] In one embodiment of the present invention, the polymerizable liquid crystal compound (B) is preferably a compound having a maximum absorption wavelength of 300 to 400 nm. Having the maximum absorption wavelength within this range is advantageous in terms of the stability of the phase difference film forming composition, and improves the orientation and uniformity of the film thickness of the resulting liquid crystal phase difference film. The maximum absorption wavelength of the polymerizable liquid crystal compound (B) can be measured in a solvent using an ultraviolet-visible spectrophotometer. The solvent is capable of dissolving the polymerizable liquid crystal compound (B), and examples include chloroform.

[0159] In the present invention, as the polymerizable liquid crystal compound (B) for forming the liquid crystal phase difference film, in addition to polymerizable liquid crystal compound (B1), or in place thereof, polymerizable liquid crystal compounds such as those described in Japanese Patent Publication No. 2010-31223, Japanese Patent Publication No. 2010-270108, Japanese Patent Publication No. 2011-6360 and Japanese Patent Publication No. 2011-207765, polymerizable liquid crystal compounds exhibiting so-called positive wavelength dispersion, polymerizable liquid crystal compound (A1) as exemplified above, etc., may be used. All of these polymerizable liquid crystal compounds can be used in either a horizontal or vertical orientation.

[0160] The content of polymerizable liquid crystal compound (B) in the phase difference film forming composition can be appropriately determined depending on the desired optical properties of the optical laminate, the type of polymerizable liquid crystal compound (B) used, etc. The content of polymerizable liquid crystal compound (B) in the phase difference film forming composition is, for example, 70 to 100 parts by mass, preferably 80 to 99 parts by mass, more preferably 85 to 98 parts by mass, and even more preferably 90 to 97 parts by mass, per 100 parts by mass of solid content of the phase difference film forming composition. If the content of polymerizable liquid crystal compound (B) is within the above range, it is advantageous from the viewpoint of the orientation of the resulting liquid crystal phase difference film.

[0161] In one embodiment of the present invention, when a composition for forming a phase difference film having a λ / 4 wave plate function contains polymerizable liquid crystal compounds other than polymerizable liquid crystal compound (B1), from the viewpoint of optical properties, the ratio of polymerizable liquid crystal compound (B1) to the total mass of all polymerizable liquid crystal compounds (B) in the phase difference film forming composition is preferably 51% by mass or more, more preferably 70% by mass or more, and even more preferably 80% by mass or more. The polymerizable liquid crystal compound (B) may all be polymerizable liquid crystal compound (B1), but from the viewpoint of liquid crystal phase transition temperature, its upper limit may be, for example, 98% by mass or 95% by mass.

[0162] The composition for forming a retardation film may contain, in addition to the polymerizable liquid crystal compound, additives such as a polymerization initiator, a solvent, and a leveling agent. As the polymerization initiator, a photopolymerization initiator that generates active radicals or acids under the action of light is preferable in that it can initiate the polymerization reaction under relatively low temperature conditions, and a photopolymerization initiator that generates radicals under the action of light is more preferable. The polymerization initiator may be used alone or in combination of two or more kinds.

[0163] As the photopolymerization initiator, a known photopolymerization initiator can be used. For example, examples of the photopolymerization initiator that generates active radicals include the same ones as those previously exemplified as usable in the composition for forming a liquid crystal polarizing film, and it may be appropriately selected in relation to the polymerizable liquid crystal compound (B) that forms the retardation film.

[0164] When the composition for forming a retardation film contains a polymerization initiator, the content of the polymerization initiator is preferably 0.1 to 20 parts by mass, more preferably 0.1 to 15 parts by mass, still more preferably 0.5 to 10 parts by mass, and particularly preferably 0.5 to 8 parts by mass, relative to 100 parts by mass of the polymerizable liquid crystal compound (B). When the content of the polymerization initiator is within the above range, the polymerization reaction can be carried out without significantly disturbing the alignment of the polymerizable liquid crystal compound.

[0165] Examples of the solvent, leveling agent and additives include the same ones as those previously exemplified as usable in the composition for forming a liquid crystal polarizing film, and each of them can be used in an amount comparable to the compounding amount in the composition for forming a liquid crystal polarizing film.

[0166] The composition for forming a retardation film can be produced by a conventionally known method for preparing a liquid crystal composition, and can usually be prepared by mixing and stirring the polymerizable liquid crystal compound (B), and optionally the polymerization initiator, the solvent, the above-mentioned additives and the like.

[0167] In the present invention, the liquid crystal phase difference film can be formed on an alignment film. Examples of alignment films include those similar to those previously exemplified for use in the production of liquid crystal polarizing films, and can be appropriately selected according to the desired alignment restricting force. In one embodiment of the present invention, a photo-alignment film is preferred from the viewpoint of ease of improving alignment accuracy and adhesion to the liquid crystal phase difference film.

[0168] The thickness of the alignment film is typically 10 to 5000 nm, preferably 10 to 1000 nm, more preferably 10 to 500 nm, even more preferably 10 to 300 nm, and particularly preferably 30 to 300 nm. When the thickness of the alignment film is within the above range, it is possible to exhibit good adhesion at the interface with the liquid crystal phase difference film formed on the alignment film while simultaneously exerting alignment-ordering force, thereby forming a polarizing film with high alignment order.

[0169] A liquid crystal phase difference film is formed, for example, by forming a coating film of a phase difference film forming composition. Removing the solvent from the aforementioned coating film, The polymerizable liquid crystal compound (B) is heated to a temperature above the temperature at which it undergoes a phase transition to the liquid phase, and then cooled to cause the polymerizable liquid crystal compound (B) to undergo a phase transition to the liquid crystal phase, and Polymerizing the polymerizable liquid crystal compound (B) while retaining the liquid crystal phase. It can be manufactured by a method that includes [a specific component].

[0170] Methods that can be used for applying the phase difference film-forming composition or curing the polymerizable liquid crystal compound (B) by light irradiation include those similar to those previously exemplified for forming the adhesive layer and the liquid crystal polarizing film.

[0171] The thickness of the liquid crystal phase difference film can be appropriately selected depending on the applicable display device. In one embodiment of the present invention, the thickness of the liquid crystal phase difference film is preferably 0.5 μm to 5 μm, and more preferably 1 μm to 3 μm.

[0172] When the laminate of the present invention includes a polarizing film, an adhesive layer, and a phase difference film adjacent to each other in this order, it can be manufactured, for example, by preparing a polarizing film, separately preparing a phase difference film, applying an adhesive composition to one side thereof to form a coating layer, laminating the coating layer and the polarizing film opposite each other, and then curing the coating layer. In this case, it is preferable to laminate the film so that the slow axis (optical axis) of the liquid crystal phase difference film and the absorption axis of the liquid crystal polarizing film are substantially 45° apart. By laminating the film so that the slow axis (optical axis) of the liquid crystal phase difference film and the absorption axis of the liquid crystal polarizing film are substantially 45° apart, the function of a circular polarizer can be obtained. In this specification, "substantially 45°" means 45° ± 5°.

[0173] <Any layer or film> The optical laminate of the present invention may further include other layers in addition to the polarizing film, adhesive layer, and optionally a phase difference film, as long as they do not affect the effects of the present invention. Examples of other layers include a protective layer for the polarizing film, an adhesive layer, and so on.

[0174] The optical laminate of the present invention exhibits excellent durability, particularly under high-temperature conditions, and is less prone to degradation of polarization performance. Furthermore, the adhesive layer contained in the optical laminate of the present invention can exhibit high adhesion to adjacent layers. When the adjacent layer opposite the polarizing film of the adhesive layer is a phase difference film, the polarizing film and the phase difference film can be laminated with high adhesion, so such an optical laminate can be suitably used as a circular polarizer, for example, as a component of an organic EL display device or the like.

[0175] A display device is a device having a display element, and includes a light-emitting element or a light-emitting device as a light source. Examples of display devices include liquid crystal displays, organic electroluminescent (EL) displays, inorganic electroluminescent (EL) displays, touch panel displays, electron emission displays [e.g., electric field emission displays (FEDs), surface field emission displays (SEDs)], electronic paper (display devices using electronic ink or electrophoretic elements), plasma displays, projection displays [e.g., grating light bulb (GLV) displays, displays having digital micromirror devices (DMDs)], and piezoelectric ceramic displays. Liquid crystal displays include transmissive liquid crystal displays, semi-transmissive liquid crystal displays, reflective liquid crystal displays, direct-view liquid crystal displays, and projection liquid crystal displays. These display devices may be displays that display two-dimensional images or stereoscopic displays that display three-dimensional images. In particular, the optical laminate of the present invention can be suitably used in organic electroluminescent (EL) displays and inorganic electroluminescent (EL) displays, and can also be suitably used in liquid crystal displays and touch panel displays. These display devices can exhibit good image display characteristics because the optical laminate of the present invention has excellent durability and can achieve high visibility. [Examples]

[0176] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to these examples. In the examples and comparative examples, "parts" and "%" refer to "parts by mass" and "% by mass" unless otherwise specified.

[0177] [Evaluation or measurement method] <Evaluation of compatibility of adhesive compositions> The adhesive compositions prepared in the examples and comparative examples (for example, adhesive composition (1) in Example 1) were stirred for 12 hours. Afterward, the uniformity of the adhesive compositions was visually confirmed, and compatibility was evaluated according to the following criteria. The results are shown in Table 1 below. A: The adhesive composition is uniform. B: Precipitation or phase separation may be observed, and the adhesive composition is not uniform.

[0178] <Measurement of viscosity of adhesive composition> The viscosity (at 25°C) of the adhesive compositions prepared in the examples and comparative examples was measured using an E-type viscometer (manufactured by Toki Sangyo Co., Ltd.) in accordance with JIS K7117-2. The results are shown in Table 1 below.

[0179] <Evaluation of coating properties of adhesive compositions> The release film on the photo-alignment film (2) side of the laminate (1) prepared in the examples and comparative examples was peeled off, and the photo-alignment film (2) was subjected to corona treatment using a corona treatment device (AGF-B10; manufactured by Kasuga Electric Co., Ltd.) under the conditions of output 0.8 kW and processing speed 10 m / min (6.9 kJ / m 2 The surface was treated with corona once. Next, the adhesive compositions prepared in the examples and comparative examples were applied to the corona-treated surface and left to stand for 10 minutes at a temperature of 23°C and a humidity of 55%. After that, the surface was visually inspected to see if the adhesive composition had been applied without any repellency or uneven thickness, and the coating properties were evaluated according to the following criteria. The results are shown in Table 1 below. A: The coating film is uniform, and there are no streaks or uneven thickness. B: Although application is possible, the desired thickness cannot be achieved, or some areas are repelled.

[0180] <Measuring thickness> Unless otherwise specified, the thickness of the layers or films contained in the fabricated optical laminates was measured using a Nikon MH-15M digital micrometer.

[0181] <Measurement of the in-plane average refractive index n2 of the adhesive layer> An adhesive composition prepared in the examples and comparative examples (for example, adhesive composition (1) in Example 1) was applied to one side of an oriented norbornene resin film (Zeonor Film manufactured by Nippon Zeon Co., Ltd.) using an adhesive coating apparatus [manufactured by Daiichi Rika Co., Ltd.] so that the thickness after ultraviolet irradiation was approximately 30 μm. Another oriented norbornene resin film was then placed over the coated surface to obtain a laminate consisting of oriented norbornene resin film / adhesive composition / oriented norbornene resin film. Next, this laminate was subjected to an ultraviolet irradiation apparatus with a belt conveyor (the lamp was a mercury lamp manufactured by I-Graphics Co., Ltd.) with an integrated light intensity of 400 mJ / cm². 2 The adhesive composition was cured by irradiating it with ultraviolet light (UV-B (280-320 nm)). The cured adhesive composition was obtained by peeling off two stretched norbornene-based resin films from the laminate after UV irradiation. The refractive index (589 nm) of the obtained cured product was measured at a temperature of 25°C using a multi-wavelength Abbe refractometer [DR-M2, manufactured by Atago Co., Ltd.], and the obtained value was adopted as the in-plane average refractive index n2 of the adhesive layer (for example, adhesive layer (1) in Example 1). The results are shown in Table 1 below.

[0182] <Relationship between the in-plane average refractive index of polarizing film, adhesive layer, and phase difference film> The in-plane average refractive index n3 of the phase difference film was measured according to the following procedure. As described below, a laminated film with a phase difference film (1) (release film / photoalignment film (2) / liquid crystal phase difference film (1)) was prepared, and the acrylic adhesive (b) layer side of a release film with an adhesive layer, consisting of a 20 μm thick acrylic adhesive (b) layer and a release film, was laminated to the phase difference film (1) side. From the resulting laminate, the release film of the release film with adhesive layer was peeled off, and the acrylic adhesive (b) layer was bonded to an alkali-free glass plate (Corning's "EagleXG") to obtain a laminate consisting of a release film / photoalignment film (2) / liquid crystal phase difference film (1) / acrylic adhesive (b) layer / alkali-free glass plate. The release film was peeled off from the resulting laminate, and the in-plane refractive index nx and ny of the phase difference film (1) at 589 nm were measured using a KOBRA-WR manufactured by Oji Instruments Co., Ltd. The in-plane average refractive index n3 of the phase difference film (1) was calculated from the following formula. n3 = (nx + ny) / 2 In the above formula, nx represents the refractive index in the direction of the slow phase axis within the plane of the phase difference film (1), and ny represents the refractive index in the direction of the fast phase axis within the plane of the phase difference film (1). The in-plane average refractive index n3 of the phase difference film (1) in Example 1 was 1.59. Next, the in-plane average refractive index n1 of the polarizing film was measured according to the following procedure. A liquid crystal polarizing film-forming composition was applied to a silicon wafer using a coating apparatus to achieve a cured film thickness of 1.8 μm. A dried film was then obtained by heating and drying in a drying oven set to 120°C for 1 minute. Next, the dried film was irradiated with ultraviolet light using a UV irradiation apparatus (under a nitrogen atmosphere, with an integrated light intensity of 500 mJ / cm² at a wavelength of 365 nm). 2 A liquid crystal polarizing film in which a polymerizable liquid crystal compound and a dichroic dye were oriented was formed on a silicon wafer by the following process. The in-plane average refractive index of the polarizing film was measured using a high-speed spectroscopic ellipsometer M-2000 (manufactured by JAWoollam). The in-plane average refractive index n1 of the polarizing film in Example 1 was 1.54. The in-plane average refractive index n3 of the phase difference film (1) and the in-plane average refractive index n1 of the polarizing film in each of the examples and comparative examples were determined in the same manner. Using the in-plane average refractive index n1 of the polarizing film, the in-plane average refractive index n2 of the adhesive layer, and the in-plane average refractive index n3 of the phase difference film (1) obtained as described above, the value of the left side of the following equation (1) was calculated. The results are shown in Table 1 below. |(n1×n3) 1 / 2 -n²| ≤ 0.070 (1)

[0183] <Durability evaluation of optical laminates> As described below, the laminate (4) prepared in Example 1 was cut to a size of 40 mm x 40 mm, the release film on the acrylic adhesive (b) layer side of the laminate (4) was peeled off, and the laminate (4) was bonded to a 40 mm x 40 mm alkali-free glass plate (Corning "EagleXG") to obtain an evaluation sample. The evaluation sample was heat-treated by standing it at a high temperature of 80°C for 168 hours. The transmittance in the transmission axis direction (Ty1) and the transmittance in the absorption axis direction (Ty2) of the evaluation sample before and after heat treatment was measured using the double-beam method with a spectrophotometer (Shimadzu Corporation UV-3150) in the wavelength range of 380 nm to 780 nm. The single-component transmittance was calculated using the following formula. Single-unit transmittance (%) = (Ty1 + Ty2) / 2 The calculated single-element transmittance was corrected for luminous sensitivity using the 2-degree field of view (C light source) of JIS Z 8701, and the luminous sensitivity-corrected single-element transmittance (Ty3) before and after heat treatment was calculated. Next, the change in luminous sensitivity-corrected single-element transmittance (ΔTy3), defined as follows, was determined. ΔTy3(%) = |Ty3(after heat treatment) - Ty3(before heat treatment)| The durability of the optical laminate was evaluated according to the following criteria. The results are shown in Table 1 below. A: ΔTy3 ≤ 3.0% B: 3.0% < ΔTy3 ≤ 10.0% C:10.0%<ΔTy3 For the optical laminates of the examples other than Example 1 and the comparative examples, the durability was evaluated using the laminate equivalent to laminate (4) in Example 1, following the procedure described above. In the case of Comparative Example 3, a float occurred during the durability test, making it impossible to determine ΔTy3.

[0184] [Example 1] <Preparation of adhesive composition> The curable compound was stirred and mixed for 30 minutes according to the composition (in parts) shown in Table 1 below. Then, the photopolymerization initiator was added and stirred and mixed for 24 hours to prepare adhesive composition (1). In Table 1, the amount of photopolymerization initiator represents the amount of solids in parts.

[0185] The abbreviations for each component used in Table 1 are as follows: • UV-7605B: Urethane acrylate oligomer (manufactured by Mitsubishi Chemical Corporation, product name "UV-7605B", viscosity: 800-1400 mPa·s / 60℃, weight-average molecular weight: 1100 g / mol, number of functional groups ((meth)acrylic groups): 6) • UV-3000B: Urethane acrylate oligomer (manufactured by Mitsubishi Chemical Corporation, product name "UV-3000B", viscosity: 40,000~60,000 mPa·s / 60℃, weight-average molecular weight: 18,000 g / mol, number of functional groups ((meth)acrylic groups): 2) • 701A: 2-Hydroxy-3-methacrylate (manufactured by Shin-Nakamura Chemical Industry Co., Ltd., product name "701A", viscosity: 44 mPa·s / 25℃, molecular weight: 214 g / mol) • 4-HBA: 4-hydroxybutyl acrylate (manufactured by Osaka Organic Chemical Industry Co., Ltd., product name "4-HBA", viscosity: 5.5 mPa·s, molecular weight: 144.2 g / mol) • HEMA: 2-Hydroxyethyl methacrylate (manufactured by Tokyo Chemical Industry Co., Ltd., trade name "2-Hydroxyethyl Methacrylate (stabilized with MEHQ)", molecular weight: 130.1 g / mol) • Acrylic acid: (Manufactured by Tokyo Chemical Industry Co., Ltd., product name "Acrylic Acid (stabilized with MEHQ), molecular weight: 72.06 g / mol) • Methacrylic acid: (Manufactured by Tokyo Chemical Industry Co., Ltd., product name "Methacrylic Acid (stabilized with MEHQ), molecular weight: 86.09 g / mol) • Mono(2-acryloyloxyethyl) succinate: Manufactured by Tokyo Chemical Industry Co., Ltd., product name "Mono(2-acryloyloxyethyl) Succinate (stabilized with MEHQ)", molecular weight: 216.19 g / mol A-LEN-10: Ethoxylated o-phenylphenol acrylate (manufactured by Shin-Nakamura Chemical Industry Co., Ltd., product name "A-LEN-10", viscosity: 130 mPa·s / 25℃, molecular weight: 268.31 g / mol, refractive index: 1.58) BA: Butyl acrylate (manufactured by Tokyo Chemical Industry Co., Ltd., product name "Butyl Acrylate (stabilized with MEHQ)", molecular weight: 128.17 g / mol) • Omnirad 819: Bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide (manufactured by IGM Resins BV, trade name "Omnirad 819", molecular weight: 418.5 g / mol, molar extinction coefficient at a light source wavelength of 400 nm in acetonitrile solvent: 1125 L·mol) -1 ·cm -1 )

[0186] <Preparation of cationic adhesive compositions> The curing component, leveling agent, and sensitizing agent listed below were stirred and mixed for 30 minutes. Then, a polymerization initiator was added and stirred and mixed for a further 24 hours to obtain a cationic adhesive composition. Note that the polymerization initiator represents the parts of solids. (curable component) 3',4'-Epoxycyclohexylmethyl 3,4-Epoxycyclohexanecarboxylate (Trade name: CEL2021P, manufactured by Daicel Corporation): 70 units • Neopentyl glycol diglycidyl ether (product name: EX-211, Nagase ChemteX Corporation): 20 units • 2-Ethylhexylglycidyl ether (Tokyo Chemical Industries, Ltd.): 10 parts (Sensitizing agent) • 1,4-Diethoxynaphthalene (leveling agent): 2.0 parts (Leveling agent) • Silicone-based leveling agent (product name: SH710, manufactured by Toray Dow Corning Co., Ltd.): 0.25 parts (Polymerization initiator) • Cationic polymerization initiator (product name: CPI-100P, 50% by mass solution, manufactured by Sunapro Co., Ltd.): 2.25 parts

[0187] <Manufacturing of optical laminates> (1) Fabrication of a laminated film with a polarizing film (i) Preparation of composition (1) for forming photoalignment film A copolymer (1) having the following structure was prepared by the following procedure. In the structure below, l, m, and n are integers between 0 and 100, and l + m + n = 100. [ka]

[0188] A solution was obtained by dissolving 4-((6-(methacryloyloxy)hexyl)oxy)benzoic acid and an amine catalyst in toluene. Chlorodimethyl ether was added dropwise to the solution, and the reaction was allowed to proceed by heating and maintaining the temperature at 40°C. After the reaction mixture was cooled, water was added. The organic layer was separated from the resulting mixture, and a 50% aqueous acetic acid solution was added to the separated organic layer and stirred to obtain a mixture. The organic layer was separated from the resulting mixture, and the separated organic layer was concentrated to obtain methoxymethyl 4-((6-(methacryloyloxy)hexyl)oxy)benzoate. 8.8 g (25.2 mmol) of methoxymethyl 4-((6-(methacryloyloxy)hexyl)oxy)benzoate, 1.0 g (3.6 mmol) of 6-(4-hydroxyphenoxy)hexyl methacrylate, 3.2 g (7.2 mol) of 4-((6-methacryloyloxy)hexyl)oxy)phenyl(E)-3-(4-methoxyphenyl)acrylate, and 0.2 g of 2,2'-azobis(2,4-dimethylvaleronitrile) were dissolved in tetrahydrofuran. After passing nitrogen through this solution for 1 hour, the reaction was allowed to proceed by heating and maintaining the temperature at 60°C, and the reaction mixture was cooled to room temperature. To this reaction mixture, 1.1 g (3.6 mmol) of 4-((6-(methacryloyloxy)hexyl)oxy)benzoic acid and 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride were added to obtain a mixture. The reaction was initiated by heating the mixture to 40°C, after which the reaction mixture was cooled. Methanesulfonic acid was added to this reaction mixture at room temperature, and after heating to 70°C, the reaction mixture was cooled to near room temperature. The cooled reaction mixture was added dropwise to n-hexane to form a precipitate, which was collected and dried under reduced pressure to obtain copolymer (1). The weight-average molecular weight of copolymer (1) was measured by GPC and found to be 24,000 g / mol. Next, 2 parts of the obtained copolymer (1) and 98 parts of propylene glycol methyl ether acetate were mixed to obtain a mixture. The obtained mixture was stirred at 80°C for 1 hour to obtain the photo-alignment film forming composition (1).

[0189] (ii) Preparation of compositions for forming liquid crystal polarizing films A composition for forming a liquid crystal polarizing film was obtained by mixing the following components and stirring at 80°C for 1 hour. The polymerizable liquid crystal compound (Y1), polymerizable liquid crystal compound (Y2), and dichroic dyes (DP1) to (DP3) each have the structures shown below. ·Polymerizable liquid crystal compound (Y1): 75 parts ·Polymerizable liquid crystal compound (Y2): 25 parts ·Dichroic dye (DP1): 2.5 parts • Dichroic dye (DP2): 2.5 parts • Dichroic dye (DP3): 2.5 parts • Polymerization initiator [2-dimethylamino-2-benzyl-1-(4-morpholinophenyl)butan-1-one (Irgacure® 369; manufactured by BASF Japan): 6 parts • Leveling agent [Polyacrylate compound (BYK-361N; BYK-Chemie Inc.)] )]: 1.2 parts • Solvent [o-xylene]: 250 parts Polymerizable liquid crystal compound (Y1) [ka] Polymerizable liquid crystal compound (Y2) [ka] Dichroic dye (DP1) [ka] Dichroic pigment (DP2) [ka] Dichroic pigment (DP3) [ka]

[0190] (iii) Fabrication of a polarizing film-coated laminated film The surface of the hard coat layer of a release film with a hard coat layer was subjected to corona treatment. A photo-alignment film-forming composition (1) was applied to the corona-treated surface using a coating apparatus, and a dried film was obtained by drying at 80°C for 1 minute. Next, the dried film was subjected to 50 mJ / cm² of polarized UV irradiation using a polarizing UV irradiation device (SPOTCURESP-9 with polarizer unit; manufactured by Ushio Inc.). 2 Polarized UV exposure with integrated light intensity (under an air atmosphere, integrated light intensity at a wavelength of 313 nm: 50 mJ / cm²) 2 A photo-aligned film (1) was formed by performing the following procedure. Furthermore, the thickness of the obtained photo-aligned film (1) was measured using an ellipsometer M-220 (manufactured by JASCO Corporation) and was found to be 100 nm. A liquid crystal polarizing film-forming composition was applied to the obtained photo-alignment film (1) using a coating apparatus, and a dried film was obtained by heating and drying in a drying oven set to 120°C for 1 minute. Next, the dried film was irradiated with ultraviolet light using a UV irradiation device (UniCure VB-15201BY-A, manufactured by Ushio Inc.) (under a nitrogen atmosphere, integrated light intensity at a wavelength of 365 nm: 500 mJ / cm²). 2 By doing so, a liquid crystal polarizing film in which a polymerizable liquid crystal compound and a dichroic dye are oriented is formed on the photo-alignment film (1), and a polarizing film-attached laminate film consisting of a release film / hard coat layer / photo-alignment film (1) / liquid crystal polarizing film is obtained. The thickness of the liquid crystal polarizing film was measured using an ellipsometer M-220 (manufactured by JASCO Corporation) and found to be 2.0 μm. Furthermore, X-ray diffraction measurements were performed on the polarizing film using an X-ray diffractometer X'PertPROMPD (manufactured by SPECTRIS Corporation). The results showed a sharp diffraction peak (Bragg peak) with a peak half-width (FWHM) of approximately 0.17° at approximately 2θ = 20.2°. The order period (d) determined from the peak position was approximately 4.4 Å, confirming the formation of a structure reflecting a higher-order smectic phase.

[0191] (2) Fabrication of laminated film with phase difference film (1) (i) Preparation of composition (2) for forming photoalignment film A photo-oriented material with the following structure (weight-average molecular weight: 50,000 g / mol, m:n=50:50) was prepared according to the method described in Japanese Patent Publication No. 2021-196514. [ka] Two parts by mass of the obtained photo-aligning material and 98 parts by mass of cyclopentanone (solvent) were mixed, and the resulting mixture was stirred at 80°C for 1 hour to prepare a photo-aligning film-forming composition (2).

[0192] (ii) Preparation of the composition (1) for forming a phase difference film Polymerizable liquid crystal compounds (X1) and (X2), having the structures shown below, were prepared, respectively. ·Polymerizable liquid crystal compound (X1): [ka] ·Polymerizable liquid crystal compound (X2): [ka] A solution was obtained by dissolving 1 mg of polymerizable liquid crystal compound (X1) in 10 mL of chloroform. The obtained solution was placed in a measuring cell with a path length of 1 cm to prepare a measurement sample, and the measurement sample was set in a UV-Vis spectrophotometer (Shimadzu Corporation "UV-2450") to measure the absorption spectrum. When the wavelength at which the maximum absorption was obtained was read from the obtained absorption spectrum, the maximum absorption wavelength λmax in the wavelength range of 300 to 400 nm was found to be 356 nm. Polymerizable liquid crystal compound (X1) and polymerizable liquid crystal compound (X2) were mixed in a mass ratio of 90:10 to obtain a mixture. To 100 parts by mass of the obtained mixture, 0.1 parts by mass of the leveling agent "BYK-361N" (manufactured by BMChemie) and 3 parts by mass of the photopolymerization initiator "Irgacure OXE-03" (manufactured by BASF Japan Ltd.) were added. Furthermore, N-methyl-2-pyrrolidone (NMP) was added to achieve a solid content concentration of 13% by mass. By stirring this mixture at a temperature of 80°C for 1 hour, a phase difference film forming composition (1) was obtained.

[0193] (iii) Preparation of laminated film with phase difference film (1) The release surface of the release film was subjected to corona treatment, and the photo-alignment film-forming composition (2) was applied to the surface of the corona-treated release film using an adhesive coating device. The resulting coating film was dried at 120°C for 2 minutes, and then cooled to room temperature to obtain a dried film. Next, the dried film was irradiated with polarized ultraviolet light at 100 mJ (313 nm reference) using a UV irradiation device (SPOTCURESP-9; manufactured by Ushio Inc.) to form a photo-alignment film (2). Furthermore, when the thickness of the photo-alignment film (2) was measured using an ellipsometer M-220 manufactured by JASCO Corporation, it was found to be 100 nm. A phase difference film-forming composition (1) was applied to the obtained photo-alignment film (2) using a coating apparatus to form a coated film. This coated film was heated and dried at 120°C for 2 minutes, then cooled to room temperature to obtain a dried film. Next, the dried film was exposed to a high-pressure mercury lamp (UniCure VB-15201BY-A, manufactured by Ushio Inc.) under a nitrogen atmosphere at an exposure dose of 500 mJ / cm². 2 By irradiating with ultraviolet light (based on 365 nm), a liquid crystal phase difference film (1) was formed on the photo-alignment film (2) in which the polymerizable liquid crystal compound was oriented horizontally with respect to the plane of the photo-alignment film (2), thereby obtaining a laminated film with a phase difference film (1). The structure of the obtained laminated film with a phase difference film (1) was release film / photo-alignment film (2) / liquid crystal phase difference film (1) (horizontally oriented liquid crystal phase difference film). The thickness of the liquid crystal phase difference film (1) was measured using a laser microscope LEXTOLS4100 manufactured by Olympus Corporation and was found to be 2.0 μm.

[0194] (3) Fabrication of laminated film with phase difference film (2) (i) Preparation of compositions for forming vertically aligned films A mixture was obtained by mixing 2-phenoxyethyl acrylate, tetrahydrofurfuryl acrylate, dipentaerythritol triacrylate, and bis(2-vinyloxyethyl) ether in a ratio of 1:1:4:5. A composition for forming vertically aligned films was obtained by mixing the obtained mixture with LUCIRINTPO as a polymerization initiator. The polymerization initiator was used in an amount of 4% by mass relative to the vertically aligned film-forming composition.

[0195] (ii) Preparation of the composition (2) for forming a phase difference film A mixed solvent was obtained by mixing methyl ethyl ketone (MEK), methyl isobutyl ketone (MIBK), and cyclohexanone (CHN) in a mass ratio (MEK:MIBK:CHN) of 35:30:35. A phase difference film-forming composition (2) was prepared by mixing 100 parts by mass of this mixed solvent with a photopolymerizable nematic liquid crystal compound (Merck KGaA, RMM28B) so that the solid content was 1 to 1.5 parts by mass.

[0196] (iii) Preparation of laminated film with phase difference film (2) A release-treated polyethylene terephthalate film (38 μm thick, release film) was coated with a vertical alignment film-forming composition on its release-treated surface, and the resulting coated film was subjected to a 200 mJ / cm² solution. 2 A vertically aligned film was formed by irradiating it with ultraviolet light. The thickness of the obtained vertically aligned film was 30 nm. A phase difference film-forming composition (2) was applied to a vertically aligned film by die coating. The resulting coated film was dried at 75°C for 120 seconds to obtain a dried film. Next, the dried film was irradiated with ultraviolet (UV) light to polymerize the polymerizable liquid crystal compound contained in the phase difference film-forming composition (2), thereby obtaining a laminated film with a phase difference film (2). The resulting laminated film with a phase difference film (2) consisted of a liquid crystal phase difference film (2), a vertically aligned film, and a polyethylene terephthalate film (release film). The thickness of the liquid crystal phase difference film (2) was measured using a laser microscope LEXTOLS4100 manufactured by Olympus Corporation and was found to be 1.0 μm.

[0197] (4) Fabrication of the laminate (1) Corona treatment was applied to the surface of the phase difference film of the laminated film with phase difference film (1) and the laminated film with phase difference film (2), and the two films were bonded together using a cationic adhesive composition so that the phase difference film (1) and the phase difference film (2) were bonded together. Next, ultraviolet light was irradiated from the side of the phase difference film (2) to cure the cationic adhesive composition and produce a laminate (1). The resulting laminate (1) consists of a release film / photo-alignment film (2) / liquid crystal phase difference film (1) / cationic adhesive layer / liquid crystal phase difference film (2) / vertical alignment film / release film.

[0198] (5) Fabrication of the laminate (2) The release film on the photo-alignment film (2) side of the laminate (1) was peeled off, and the surface of the photo-alignment film (2) was subjected to corona treatment. The adhesive composition (1) was applied to the corona-treated surface using a coating apparatus to form a coated layer (1). Next, the polarizing film surface of the polarizing film-attached laminate film was subjected to corona treatment, and the corona-treated surface was placed opposite the coated layer (1) and laminated. From the phase difference film (2) side of the obtained laminate, an ultraviolet irradiation device with a belt conveyor (the lamp is a mercury lamp manufactured by I-Graphics Co., Ltd.) was used to apply an integrated light intensity of 450 mJ / cm². 2 The adhesive composition (1) was cured by irradiation with UV light (UV-V (395-445 nm; the same applies hereinafter)), thereby obtaining a laminate (2). The composition of the obtained laminate (2) was: release film / hard coat layer / photoalignment film (1) / liquid crystal polarizing film / adhesive layer (1) [cured layer of adhesive composition (1)] / photoalignment film (2) / liquid crystal phase difference film (1) / cationic adhesive layer / liquid crystal phase difference film (2) / vertical alignment film / release film. The thickness of the adhesive layer (1) was 2 μm.

[0199] (6) Fabrication of laminate (3) (circular polarizer) The release film on the hard coat layer side of laminate (2) was peeled off, and the surface of the hard coat layer was subjected to corona treatment. The acrylic adhesive (a) layer side of a release film with an adhesive layer, consisting of a 5 μm thick acrylic adhesive (a) layer and a release film, was laminated onto the corona-treated surface. Furthermore, the release film of the release film with an adhesive layer was peeled off, and the acrylic adhesive (a) layer was laminated facing the corona-treated surface of a 25 μm thick norbornene resin film (Zeonor Film ZF-14 manufactured by Nippon Zeon Co., Ltd.) that had been corona-treated on one side, thereby obtaining laminate (3). The composition of laminate (3) is norbornene resin film / acrylic adhesive (a) layer / hard coat layer / photo-alignment film (1) / liquid crystal polarizing film / adhesive layer (1) / photo-alignment film (2) / liquid crystal phase difference film (1) / cationic adhesive layer / liquid crystal phase difference film (2) / vertical alignment film / release film.

[0200] (7) Fabrication of laminate (4) (circular polarizing plate with adhesive layer) The release film on the vertical alignment film side of the laminate (3) was peeled off, and the surface of the vertical alignment film was subjected to corona treatment. Laminate (4) was obtained by laminating the acrylic adhesive (b) layer side of a release film with an adhesive layer, which consists of an acrylic adhesive (b) layer with a thickness of 20 μm and a release film, onto the corona-treated surface. The structure of laminate (4) is norbornene resin film / acrylic adhesive (a) layer / hard coat layer / photo-alignment film (1) / liquid crystal polarizing film / adhesive layer (1) / photo-alignment film (2) / liquid crystal phase difference film (1) / cationic adhesive layer / liquid crystal phase difference film (2) / vertical alignment film / acrylic adhesive (b) layer / release film.

[0201] [Examples 2-7, Comparative Examples 1-3] Laminates and optical laminates were prepared in the same manner as in Example 1, except that adhesive compositions (2) to (7) and adhesive compositions (1') to (3') were prepared with the compositions shown in Table 1 below, instead of adhesive composition (1), and adhesive compositions (2) to (7) and adhesive compositions (1') to (3') were used instead of adhesive composition (1). The adhesive compositions or optical laminates were then evaluated or measured.

[0202] [Examples 8-10] Laminates and optical laminates were prepared in the same manner as in Example 1, except that adhesive compositions (8) to (10) with the compositions shown in Table 1 below were prepared instead of adhesive composition (1), and adhesive compositions (8) to (10) were used instead of adhesive composition (1). The adhesive compositions or optical laminates were then evaluated or measured.

[0203] [Table 1]

Claims

1. An adhesive composition containing a curable compound, The curable compound is (A) A urethane acrylate compound having two or more (meth)acrylic groups and a weight-average molecular weight of 1000 g / mol or more. (B) A (meth)acrylate compound having two or more (meth)acrylic groups and a hydroxyl group in the molecule, (C) A (meth)acrylate compound having one (meth)acrylic group and a hydroxyl group in the molecule, and (D) Compounds that do not have a hydroxyl group in the molecule but have a carboxyl group and a polymerizable group. An adhesive composition containing the following:

2. The adhesive composition according to claim 1, further comprising a (meth)acrylate compound (E) having one (meth)acrylic group, no hydroxyl group in the molecule, and having an aromatic ring.

3. The adhesive composition according to claim 1, wherein the content of the urethane acrylate compound (A) is 3 to 30 parts by mass per 100 parts by mass of the total amount of curable compounds contained in the adhesive composition.

4. The adhesive composition according to claim 1, wherein the content of the (meth)acrylate compound (B) is 3 to 30 parts by mass per 100 parts by mass of the total amount of curable compounds contained in the adhesive composition.

5. The adhesive composition according to claim 1, wherein the content of the (meth)acrylate compound (C) is 15 to 80 parts by mass per 100 parts by mass of the total amount of curable compounds contained in the adhesive composition.

6. The adhesive composition according to claim 1, wherein the content of compound (D) is 5 to 45 parts by mass per 100 parts by mass of the total amount of curable compounds contained in the adhesive composition.

7. The adhesive composition according to claim 2, wherein the content of the (meth)acrylate compound (E) is 5 to 25 parts by mass per 100 parts by mass of the total amount of curable compounds contained in the adhesive composition.

8. The adhesive composition according to claim 1, further comprising a polymerization initiator, wherein the content of the polymerization initiator is 1 to 10 parts by mass per 100 parts by mass of the total amount of curable compounds contained in the adhesive composition.

9. The polymerization initiator has a molar extinction coefficient of 10 L·mol in acetonitrile solvent at a light source wavelength of 400 nm. -1 ・cm -1 The adhesive composition according to claim 8.

10. An optical laminate comprising a polarizing film and an adhesive layer adjacent to each other, The polarizing film comprises a cured layer of a polymerizable liquid crystal composition containing a polymerizable liquid crystal compound and a dichroic dye. The optical laminate is an optical laminate in which the adhesive layer is a cured product layer of the adhesive composition described in claim 1.

11. The optical laminate according to claim 10, wherein the adhesive layer contains a phase difference film adjacent to the side opposite to the polarizing film, and the phase difference film contains a cured layer of a polymerizable liquid crystal composition containing a polymerizable liquid crystal compound.

12. The optical laminate according to claim 11, wherein the phase difference film includes an alignment film, and the alignment film is located on the adhesive layer side.

13. When the in-plane average refractive index of the polarizing film is n1, the in-plane average refractive index of the adhesive layer is n2, and the in-plane average refractive index of the liquid crystal phase difference film is n3, then the following equation (1): |(n1×n3) 1/2 --2| ≦ 0.070 (1) The optical laminate according to claim 11, satisfying the requirements.

Citation Information

Patent Citations

  • Polarizing film and method for producing the same

    JP2020056834A